Reagent layer containing conductive carbon filler, sensor having same, and method for forming same

By using a reagent layer containing conductive carbon filler, anionic dispersant and cationic media in an electrochemical sensor, the problem of difficulty in dispersing conductive carbon filler in an aqueous solvent is solved, and high sensitivity and durability of electricity is achieved Chemical sensor.

CN119487389APending Publication Date: 2025-02-18PHC HLDG CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380051345.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-01
Filing Date
2023-06-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The conductive carbon filler is difficult to disperse and maintain a dispersed state in the aqueous solvent, resulting in a reduced detection sensitivity of the sensor and insufficient durability.

Method used

A reagent layer containing conductive carbon filler, anionic dispersant and cationic media is used to prepare the reagent solution under specific conditions to avoid aggregation and precipitation of conductive carbon particles and ensure a good dispersion state.

Benefits of technology

The good dispersion of conductive carbon fillers in aqueous solvents is achieved, and the detection sensitivity and durability of electrochemical sensors are improved, especially in long-term measurements in humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention addresses the problem of providing a reagent layer for producing an electrochemical sensor which can detect an analyte with high sensitivity and / or is suitable for long-term measurement (continuous monitoring) and has excellent durability, and a method for forming the reagent layer. The reagent layer of the present invention contains a conductive carbon filler (a), an anionic dispersant (b), and a cationic mediator (c). This method for forming a reagent layer comprises: (1) a step for preparing a reagent solution containing a conductive carbon filler (a), an anionic dispersant (b), and a cationic mediator (c); (2) a step for applying the reagent solution to a site where a reagent layer is formed; and (3) a step for forming a reagent layer by drying the applied reagent solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a reagent layer and a sensor containing a conductive carbon filler. More specifically, the present invention relates to a conductive carbon filler dispersant as a reagent for improving the dispersibility of the conductive carbon filler in an aqueous solvent, a reagent layer containing the dispersant, the conductive carbon filler and a cationic mediator, a sensor having the reagent layer, and a method for forming the reagent layer. Background Art

[0002] In the past, it is known that there are sensors that measure the analyte after allowing protein to act on the analyte in the sample. As such a sensor, an electrochemical sensor using an enzyme can be cited, such as a glucose sensor made using glucose oxidoreductase and a redox mediator (a redox substance that mediates electron transfer) used as needed, a redox polymer (a polymer that is bonded to the redox mediator via a joint, etc.). Glucose sensors are used, for example, for self-detection of blood sugar levels. In the past, glucose sensors that usually collect trace amounts of blood as samples have also been developed in recent years. Implantable electrochemical glucose sensors that are implanted in a living body and continuously measure glucose in the blood or in the interstitium have also been developed. In addition, glucose sensors are also used to measure glucose in samples outside biological substances, such as culture media. Such glucose sensors usually measure the glucose concentration in a sample continuously or semi-continuously for a long period of several days to several weeks.

[0003] In recent years, in order to achieve high sensitivity and high output by increasing the specific surface area of ​​the electrode, conductive carbon fillers such as nanocarbon materials with high specific surface area are used in electrodes used in glucose sensors represented by electrochemical glucose sensors and biofuel cells. For example, Patent Document 1 discloses a sensor made of a carbon black dispersion using hydroxypropyl cellulose, and Patent Document 2 discloses an enzyme-immobilized electrode using ethyl cellulose and carbon particles as a binder.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-082394

[0007] Patent Document 2: WO2013 / 065581 Summary of the invention

[0008] Problems to be solved by the invention

[0009] Usually, in order to form a reagent layer including a conductive carbon filler and a redox mediator or a redox polymer, and further including a redox enzyme, etc. as required, a reagent solution in which these essential components are dispersed in an aqueous solvent is prepared, the reagent solution is applied to a desired position, and dried. However, since the conductive carbon filler is usually highly hydrophobic, it is difficult to be dispersed in an aqueous solvent. In addition, since it is easy to condense due to van der Waals forces, it is difficult to maintain a dispersed state. In the case of using a reagent solution in which the conductive carbon filler is not fully dispersed to form a reagent layer, it will cause a significant reduction in the detection sensitivity of the analyte or a lack of durability in a long-term determination (continuous monitoring) in a humid environment such as in a living body or a culture medium. It should be noted that it is appropriate to dissolve the redox enzyme in an aqueous solvent, and it is not appropriate to use an organic solvent as a solvent for preparing the reagent solution.

[0010] One aspect of the present invention is to provide a reagent layer for making an electrochemical sensor capable of detecting an analyte with high sensitivity and a method for forming the same. Another aspect of the present invention is to provide a reagent layer for making an electrochemical sensor suitable for long-term measurement (continuous monitoring) and having excellent durability and a method for forming the same.

[0011] Means for solving problems

[0012] The inventors of the present application have discovered the following situations, among others: in a reagent solution using a conductive carbon filler and a cationic redox mediator or a redox polymer (cationic mediator) and an anionic dispersant, and preferably prepared under specific conditions, no aggregation or precipitation of the conductive carbon particles occurs, and the dispersion state is good; the reagent layer formed using such a reagent solution enables the cationic mediator to be closely adsorbed onto the electrode, so that the detection sensitivity of the electrochemical sensor for the analyte is improved, and the durability for continuous monitoring is excellent, thereby completing the present invention.

[0013] That is, the present invention includes at least the following matters.

[0014] [Item 1]

[0015] A reagent layer comprises a conductive carbon filler (a), an anionic dispersant (b) and a cationic mediator (c).

[0016] [Item 2]

[0017] The reagent layer according to item 1, wherein the anionic dispersant (b) is a polymer having a weight average molecular weight of 70,000 or less.

[0018] [Item 3]

[0019] The reagent layer according to item 1, wherein the anionic dispersant (b) is a polymer having a carboxyl group and / or a sulfonic group in a side chain.

[0020] [Item 4]

[0021] The reagent layer according to item 3, wherein the anionic dispersant (b) is a polymer containing at least one selected from the group consisting of a unit derived from acrylic acid, a unit derived from maleic acid, and a unit derived from styrenesulfonic acid.

[0022] [Item 5]

[0023] The reagent layer according to item 1, wherein the cationic mediator (c) is a compound in which a redox mediator compound (c1) and a cationic polymer (c2) are bonded via a linker (c3) as needed.

[0024] [Item 6]

[0025] The reagent layer according to item 5, wherein the cationic polymer (c2) has a quaternary ammonium cationic group.

[0026] [Item 7]

[0027] The reagent layer according to item 1, wherein the conductive carbon filler (a) is carbon black.

[0028] [Item 8]

[0029] The reagent layer according to item 1, further comprising an oxidoreductase (e) for oxidizing or reducing the analyte.

[0030] [Item 9]

[0031] The reagent layer according to Item 8, wherein the oxidoreductase (e) is a coenzyme-binding oxidoreductase.

[0032] [Item 10]

[0033] The reagent layer according to Item 8, wherein the oxidoreductase (e) is cross-linked with the cationic polymer (c2).

[0034] [Item 11]

[0035] An electrochemical sensor for detecting or quantifying an analyte, comprising a working electrode, a counter electrode, and a reagent layer as described in any one of items 1 to 10.

[0036] [Item 12]

[0037] The electrochemical sensor according to Item 11, further comprising a reference electrode.

[0038] [Item 13]

[0039] The electrochemical sensor according to Item 11, further comprising a protective film covering at least the reagent layer.

[0040] [Item 14]

[0041] A method for forming a reagent layer, the method comprising:

[0042] (1) a step of preparing a reagent solution containing a conductive carbon filler (a), an anionic dispersant (b), and a cationic mediator (c);

[0043] (2) applying the reagent solution to the reagent layer formation site; and

[0044] (3) A step of drying the applied reagent solution to form a reagent layer.

[0045] [Item 15]

[0046] The method for forming a reagent layer according to Item 14, wherein the pH of the reagent solution is 8.0 or less.

[0047] [Item 16]

[0048] The method for forming a reagent layer according to Item 15, wherein the concentration of the metal ions in the reagent solution is 200 mM or less.

[0049] [Item 17]

[0050] The method for forming a reagent layer according to item 16, wherein the metal ions in the reagent solution are alkali metal ions and the concentration thereof is less than 100 mM.

[0051] [Item 18]

[0052] The method for forming a reagent layer according to item 14, wherein the anionic dispersant (b) is a polymer having a weight average molecular weight of 70,000 or less and comprising at least one selected from the group consisting of a unit derived from acrylic acid, a unit derived from maleic acid, and a unit derived from styrenesulfonic acid.

[0053] [Item 19]

[0054] The method for forming a reagent layer according to item 14, wherein the cationic mediator (c) is a compound in which a redox mediator compound (c1) and a cationic polymer (c2) having a quaternary ammonium cationic group are bonded via a linker (c3) as needed.

[0055] Effects of the Invention

[0056] The present invention can make the conductive carbon filler well dispersed in the reagent solution containing the aqueous solvent. In addition, by using such a reagent solution (carbon dispersion solution) in which the conductive carbon filler is dispersed, an electrochemical sensor with excellent practicality can be produced, which achieves high sensitivity and improved durability (for example, the performance of maintaining responsiveness during the measurement in a humid environment) despite containing the conductive carbon filler.

[0057] It should be noted that in the present invention, whether the conductive carbon material is "dispersed" (including "redispersed") or "aggregated" (including "aggregated / precipitated") in the reagent solution can be judged visually in most cases. For example, when the conductive carbon material is "aggregated", floating or precipitated aggregates can be easily confirmed visually.

[0058] When determining the dispersion and aggregation of the conductive carbon filler, centrifugal separation can also be used. For example, when the reagent solution in which the conductive carbon filler is "dispersed" is centrifuged, no precipitation of the conductive carbon filler occurs, but when the reagent solution in which the conductive carbon filler is "aggregated" is centrifuged, the aggregates are precipitated and separated into a layer of the conductive carbon filler and a transparent aqueous solution phase. The processing conditions for centrifugal separation can be set to 10,000×g for 5 minutes, for example, but can also be appropriately adjusted according to the embodiment, for example, considering the type and concentration of the conductive carbon filler. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 It is a top view of a sensor according to one embodiment of the present invention. Figure 1 (A) represents the sensor as a whole, Figure 1 (B) An enlarged view of the front end of the sensor.

[0060] Figure 2 yes Figure 1 (B) Cross-sectional view of a specific portion of the sensor. Figure 2 (A) Yes Figure 1 (B) Sectional view taken along the AA line. Figure 2 (B) Yes Figure 1 (B) Cross-sectional view taken along arrow BB. Figure 2 (C) Yes Figure 1 (B) Cross-sectional view taken along arrow CC.

[0061] Figure 3 This is a plan view showing another example of the front side (the side having the working electrode and the reference electrode) of the sensor according to one embodiment of the present invention.

[0062] Figure 4 yes Figure 3 Cross-sectional view at the A-A' cutting line.

[0063] Figure 5 yes Figure 4 Cross-sectional view at the BB' cutting line.

[0064] Figure 6 yes Figure 4 Cross-sectional view at the C-C' cutting line.

[0065] Figure 7 It is a top view of a sensor according to one embodiment of the present invention. Figure 7 (A) shows an electrode pattern before film (insulating resist film) formation, Figure 7 (B) shows the electrode pattern after film formation.

[0066] Figure 8 These are images of recovered liquid samples reflecting the dispersion effect of carbon black from various reagent liquid samples prepared in Test Example 1. [A] corresponds to recovered liquid samples of reagent liquid samples 1-1 to 1-8. [B] corresponds to recovered liquid samples of reagent liquid samples 1-9 to 1-11.

[0067] Fig. 9 The results of measuring the responsiveness of the sensor of Test Example 6 are shown. [A] Results of current response value. [B] Results of cyclic voltammetry.

[0068] Fig.10 The following are the results of measuring the durability of the sensor of Test Example 7. [A] Results for a sensor produced using poly(acrylic acid). [B] Results for a sensor produced using hydroxypropyl cellulose.

[0069] Description of Reference Numerals

[0070] 11 sensor (probe), 21 substrate, 22 electrode, 22a working electrode, 22b reference electrode, 22c counter electrode, 23 reagent layer, 24 silver / silver chloride layer, 25 membrane, X1 sensor head, X2 sensor insertion direction into biological body, X3 region of counter electrode not covered by membrane, X4 region of sensor head not covered by membrane, X5 region where reagent layer is not formed, X6 region where reagent layer and electrode (working electrode) are not formed (trimmed), 101 sensor, 111 insulating substrate, 112 conductive film, 112a working electrode region, 112b reference electrode region, 112c counter electrode region, 113 groove, 114 working electrode, 115 reference electrode, 116a insulating resist film (upper surface), 116b insulating resist film (lower surface), 117 counter electrode, 118 reagent layer, 119 protective film, 121 sensing portion, 122 terminal portion, 201 sensor, 202 sensing portion, 203 terminal portion, 204 notch portion, 210 substrate, 220 electrode, 221 first working electrode, 221a exposed region of the sensing portion of the first working electrode, 221b exposed region of the terminal portion of the first working electrode, 222 second working electrode, 222a exposed region of the sensing portion of the second working electrode, 222b exposed region of the terminal portion of the second working electrode, 223 reference electrode, 223a exposed region of the sensing portion of the reference electrode, 223b exposed region of the terminal portion of the reference electrode, 224 counter electrode, 224a exposed region of the sensing portion of the counter electrode, 224b exposed region of the terminal portion of the counter electrode, 225 groove, 230 film (insulating resist film). DETAILED DESCRIPTION

[0071] ― Reagent layer ―

[0072] The reagent layer of the present invention comprises a conductive carbon filler (a), an anionic dispersant (b) and a cationic mediator (c). The reagent layer of the present invention is a layer that can be formed by a formation method using a carbon dispersion liquid as described later, that is, a reagent liquid in which the conductive carbon filler (a) is dispersed, and preferably a layer in which the conductive carbon filler (a), the anionic dispersant (b) and the cationic mediator (c) are in a uniform state.

[0073] (a) Conductive carbon filler

[0074] The "conductive carbon filler" of the present invention is not limited to a specific type, and various conductive carbon fillers can be used in consideration of the embodiment of the present invention (reagent layer, electrochemical sensor application, etc.), the effect, etc. As the conductive carbon filler, conductive carbon materials in various shapes such as spherical (particle), flaky, fibrous, and porous can be used. The conductive carbon filler (a) can be used alone or in combination (for example, mixed).

[0075] As conductive carbon fillers, for example, carbon black, graphite powder, porous carbon materials, nanocarbon materials, etc. can be cited. Specific examples of carbon black include furnace black, pyrolytic carbon black, acetylene black, Ketjen black, and channel black. Specific examples of graphite powder include pyrolytic graphite and spherical graphite. Specific examples of porous carbon materials include not only activated carbon powder or activated carbon fibers having mesopores of 2 to 50 nm, but also carbon materials having interconnected pores connected by mesopores. Specific examples of nanocarbon materials include single-layer carbon nanotubes, multi-layer carbon nanotubes, graphene, fullerene, carbon nanohorns, and carbon nanocoils. The size of the conductive carbon filler (a) can be within an appropriate range. For example, when the conductive carbon filler is spherical (particulate), its average particle diameter (for example, the average value measured for a given number of particles using an electron microscope) is usually in the range of 10 nm to 20 μm. The BET specific surface area of ​​the conductive carbon filler is, for example, 10 m 2 / g or more, preferably 30m 2 The conductive carbon filler (a) of the present invention is preferably a spherical (particulate) carbon filler, such as carbon black.

[0076] (b) Anionic dispersants

[0077] In the present invention, the term "anionic dispersant" refers to a compound having an essential function of dispersing the conductive carbon filler (a) in the reagent solution and having a negative charge (anionic) as the net charge of the molecule as a whole. The anionic dispersant (b) may be used alone or in combination (e.g., as a mixture).

[0078] However, "anionic surfactants" and "anionic polysaccharides" do not correspond to the anionic dispersant (b) of the present invention. Examples of anionic surfactants include methylnaphthalenesulfonic acid formaldehyde condensate salts (e.g., methylnaphthalenesulfonic acid formaldehyde condensate sodium salt, product name "DEMOL MS" (Kao)), naphthalenesulfonic acid formaldehyde condensate salts (e.g., β-naphthalenesulfonic acid formaldehyde condensate sodium salt, product name "DEMOL N" (Kao)), alkylene maleic acid copolymer salts (e.g., diisobutylene-maleic anhydride copolymer sodium salt, product name "DEMOL EP" (Kao)), sodium lauryl sulfate, sodium cholate, and sodium deoxycholate. Examples of anionic polysaccharides include anionic cellulose derivatives such as carboxymethyl cellulose, anionic guar gums such as carboxymethylated guar gum, and xanthan gums. Such anionic surfactants or anionic polysaccharides are not used as the anionic dispersant (b) of the present invention.

[0079] The electrochemical sensor of a specific embodiment of the present invention has a protective film covering the reagent layer formed on the sensor (working electrode). In such an embodiment, in order to prevent the anionic dispersant (b) from flowing out of the protective film (in vivo, culture medium, etc.), after the protective film is formed, the sensor (working electrode) can be pre-immersed in an aqueous solvent, thereby dissolving and removing the anionic dispersant (b) from the reagent layer. In such a treatment, due to the relationship between the size and molecular weight of the pores of the protective film, for example, the anionic dispersant (b) combined with the conductive carbon filler (a) will not / is difficult to dissolve from the reagent layer (dissolve outside the protective film), but the anionic dispersant (b) that is not combined with the conductive carbon filler (a) dissolves from the reagent layer (dissolves outside the protective film). It should be noted that as the aqueous solvent in this treatment, the same aqueous solvent as the aqueous solvent used for preparing the reagent solution used in the method for forming the reagent layer of the present invention described later can be used.

[0080] For example, an "anionic polymer" (excluding polymers that meet the requirements of anionic surfactants and anionic polysaccharides) that has an essential function of dispersing the conductive carbon filler (a) in the reagent solution and has a negative charge as the net charge of the polymer as a whole can be used as the anionic dispersant (b) in the present invention. The anionic polymer can be a straight chain, branched chain, comb-shaped, or any "chain structure", and the "chain structure" can contain one or more ring structures derived from cyclic compounds (aromatic hydrocarbon rings, non-aromatic hydrocarbon rings, aromatic heterocycles, non-aromatic heterocycles, etc.). The main chain (the part of the polymer with a relatively long length in the chain structure) and the side chain (the part of the polymer with a relatively short length in the chain structure) of the anionic polymer are usually mainly composed of carbon atoms, and can contain at least one hetero atom selected from nitrogen atoms, oxygen atoms, and sulfur atoms. In other words, there can be ether bonds, thioether bonds, amide bonds, etc. containing hetero atoms in the middle. Anionic polymers may generally have two or more (plural) negatively charged functional groups (anionic functional groups) in the side chain, and may further have anionic functional groups at one or both ends of the main chain. Various anionic polymers are known as anionic polymers having anionic functional groups in the side chain and / or at the end, and anionic polymers having the desired properties may be purchased, produced by changing appropriate polymers, or synthesized using appropriate monomers. Anionic polymers may be any of homopolymers, copolymers, and polymers obtained by bonding and / or mixing them, and may also be any of random polymers, block polymers, and graft polymers.

[0081] Examples of the anionic functional group include a carboxyl group which may have a substituent, preferably an unsubstituted carboxyl group which generates -COO in an aqueous solvent. - A group, a sulfo group which may have a substituent, preferably an unsubstituted sulfo group, which generates -SO3 in an aqueous solvent - The group.

[0082] Examples of anionic polymers include olefinic polymers having anionic functional groups in side chains (and at the ends). Examples of olefinic polymers include homopolymers and copolymers synthesized from one or more monomers selected from monomers containing olefinic carbon-carbon double bonds capable of free radical polymerization, such as vinyl (CH2=CH-), allyl (CH2=CH-CH2-), acryloyl (CH2=CH-C(O)-), methacryloyl (CH2=C(CH3)-C(O)-), and their modifications (e.g., units derived from vinyl acetate are vinylated by saponification, and hydrophilicity-imparting treatment is performed). Examples of the monomer containing an olefinic carbon-carbon double bond include ethylene, propylene, butadiene, isobutylene, tetrafluoroethylene, vinyl alcohol, vinyl acetate, vinyl chloride, vinylidene chloride, styrene, methylstyrene, allylamine, diallylamine, diallyldimethylammonium chloride, acrylic acid, methacrylic acid, methyl acrylate (also called methyl acrylate), methyl methacrylate (also called methyl methacrylate), butyl acrylate (also called butyl acrylate), butyl methacrylate (also called butyl methacrylate), hydroxyethyl methacrylate, and acrylonitrile.

[0083] In one embodiment of the present invention, the anionic dispersant (b) is a polymer comprising at least one selected from the group consisting of units derived from acrylic acid, units derived from maleic acid, and units derived from styrene sulfonic acid, i.e., a homopolymer or copolymer synthesized using at least one monomer selected from the group consisting of acrylic acid, maleic acid, and styrene sulfonic acid (e.g., 4-styrene sulfonic acid). It should be noted that the copolymer may be a copolymer synthesized using at least one monomer selected from the group consisting of acrylic acid, maleic acid, and styrene sulfonic acid (e.g., 4-styrene sulfonic acid) and a monomer other than at least one selected from the group consisting of acrylic acid, maleic acid, and styrene sulfonic acid (e.g., 4-styrene sulfonic acid).

[0084] In one embodiment of the present invention, the anionic dispersant (b) is a polymer having a carboxyl group and / or a sulfonic group as an anionic functional group in a side chain.

[0085] Examples of the polymer that can be used in either of the two embodiments and is preferably used as the anionic dispersant (b) of the present invention include poly(acrylic acid), poly(styrene sulfonic acid), poly(styrene sulfonic acid-co-maleic acid), poly(ethylene oxide)-b-poly(acrylic acid), and poly(styrene)-b-poly(acrylic acid).

[0086] The degree of polymerization, weight average molecular weight, other properties, characteristics, etc. of the anionic polymer used as anionic dispersant (b) can be adjusted according to the embodiment of the present invention, the effect of action, and the type of anionic polymer. The degree of polymerization of the anionic polymer is usually 50 or more. Regarding the average molecular weight of the anionic polymer, the weight average molecular weight is representatively, for example, 1000 or more, preferably 5000 or more. The upper limit of the weight average molecular weight of the anionic polymer is not particularly limited, but for example, it is 100000 or less, preferably 70000 or less.

[0087] It should be noted that the weight average molecular weight and molecular weight distribution of the anionic polymer can be measured by a known method according to the type of the anionic polymer, for example, gel permeation chromatography (GPC) can be used. In addition, when a commercially available product is purchased as an anionic polymer and used, the numerical value given in its product catalogue (for example, in the form of "Mw" or "MW") can be regarded as the weight average molecular weight.

[0088] (c) Cationic mediators

[0089] In the present invention, the term "cationic mediator" refers to a compound (redox mediator compound) having the essential function of being a redox mediator, or a compound (cationic) containing a site from such a redox mediator compound and having a positive charge as the net value of the molecule as a whole. It should be noted that the term "redox mediator" refers to a redox substance that mediates electron transfer, for example, a substance that is responsible for the transfer of electrons generated by the redox reaction of the analyte based on the redox enzyme. Cationic mediators can be used alone or in combination of two or more.

[0090] In a preferred embodiment of the present invention, the cationic mediator (c) is a compound having a structure in which a "redox mediator compound" (c1) and a "cationic polymer" (c2) are bonded via a "linker" (c3) as required. The "cationic mediator" of the present invention, i.e., the "redox mediator", "cationic polymer", and "linker" used to constitute it are not limited to specific types, and various substances can be used in consideration of the embodiments, effects, etc. of the present invention.

[0091] (c1) Redox mediator compound

[0092] The "redox mediator compound" of the present invention is not limited to a specific type, and various redox mediators or derivatives thereof can be used in consideration of the embodiment (reagent layer, use of electrochemical sensor, etc.), action effect, etc. of the present invention.

[0093] Examples of the redox mediator compound include phenazine compounds, phenothiazine compounds, osmium complexes, ruthenium complexes, quinone compounds, and ferrocene compounds.

[0094] In one embodiment of the present invention, the redox mediator compound is a phenazine compound or a phenothiazine compound. Since the redox potential (vs. Ag / AgCl·saturated KCl) of phenazine compounds and phenothiazine compounds is negative (lower than 0V), they are not easily affected by inclusions in the sample for electrochemical measurement, such as ascorbic acid (vitamin C) and uric acid contained in biological samples or culture medium samples, which are not considered as analytes, and thus can be said to be preferred redox mediators.

[0095] The phenazine compounds and phenothiazine compounds are compounds represented by the following general formulas (1) and (2), respectively, having a phenazine skeleton or a phenothiazine skeleton, and capable of acting as a redox mediator. For example, in the phenothiazine compound represented by the general formula (2), R 3 For the formula -NR 31 R 32 The substituted amino group represented by 31 and R 32 Both are substituents, or either one is a substituent and the other is a hydrogen atom. ), the phenothiazine compound becomes a compound having resonance structures of the following general formulae (2-1) and (2-2) and serving as a cationic mediator alone.

[0096] [Chemistry 1]

[0097]

[0098] (1) Phenazine compounds (2) Phenothiazine compounds

[0099] [Chemistry 2]

[0100]

[0101] In general formulas (1) and (2), R 1 ~R 9Each independently represents any group or atom of the following (i) to (ix') (wherein (ix') is limited to the case where the cationic mediator (c) is a compound having a structure in which a "redox mediator compound" (c1) and a "cationic polymer" (c2) are bonded via a "linker" (c3) as required, that is, (ix') is limited to the case where a specific reactive group (described in detail later) of a phenazine compound or a phenothiazine compound as the redox mediator compound (c1) reacts with a specific reactive group of a cationic polymer (c2) or a specific reactive group of a linker compound):

[0102] (i) hydrogen atoms;

[0103] (ii) halogen atoms;

[0104] (iii) a hydroxy group which may have a substituent;

[0105] (iv) an amino group which may have a substituent;

[0106] (v) a saturated or unsaturated hydrocarbon group which may have a substituent (e.g., C 1-15 Alkyl, preferably C 1-6 alkyl);

[0107] (vi) an acyl group which may have a substituent (e.g., C 1-6 Acyl, i.e. C 1-6 alkyl-carbonyl);

[0108] (vii) a phenyl group which may have a substituent;

[0109] (viii) quaternary ammonium cationic groups;

[0110] (ix) a carboxyl group that has been actively esterified (for example, a carboxyl group that has been actively esterified by N-hydroxysuccinimide (NHS));

[0111] (ix') carboxyl group.

[0112] Examples of the substituents that the substituents (iii) to (vii) may have include (a) halogen atoms, (b) hydroxyl groups, (c) amino groups, (d) linear or branched saturated or unsaturated hydrocarbon groups (e.g., C 1-15 Alkyl, preferably C 1-6 Alkyl, more preferably C 1-3 alkyl), (e) acyl (e.g. C 1-6 Acyl, preferably C 1-3(c1) and (c2) are preferably selected from the group consisting of: (i) acyl group, (f) guanidine group, (g) methanesulfonyl group, (h) phenyl group, (i) thiol group, (j) formyl group (aldehyde group), (k) epoxy group, (l) maleimide group, (m) carboxyl group after active esterification, (m') carboxyl group, and (n) oxyethylene group. However, (m') is limited to the case where the cationic mediator (c) is a compound having a structure in which a "redox mediator compound" (c1) and a "cationic polymer" (c2) are bonded via a "linker" (c3) as required, that is, (m') is limited to the case where the specific reactive group of the phenazine compound or phenothiazine compound (described in detail later) as the redox mediator compound (c1) reacts with the specific reactive group of the cationic polymer (c2) or the specific reactive group of the linker compound. The substituents that the substituents of (iii) to (vii) may have may be a group consisting of any one of (a) to (n) alone, or may be a group consisting of two or more selected from (a) to (n), for example, a group further substituted with (c) an amino group, (i) a thiol group, (j) a formyl group, (k) an epoxy group, (l) a maleimide group, (m) an active esterified carboxyl group, or (n) an oxyethylene group, or (d) a linear or branched saturated or unsaturated hydrocarbon group. Those skilled in the art can implement the present invention by selecting a chemically appropriate substituent from (a) to (n) for each of (iii) to (vii), or by selecting and combining two or more chemically appropriate substituents from (a) to (n). The number of substituents that each of the above (iii) to (vii) may have is not particularly limited, and may be, for example, 1, 2 or 3. In addition, a plurality of substituents may be bonded to one atom (eg, a carbon atom of an alkyl group, a nitrogen atom of an amino group).

[0113] It should be noted that the quaternary ammonium cationic group (viii) refers to a quaternary ammonium cationic group with -R A -N + (R B )(R C )(R D ) represented by a group (wherein R A , R B , R C and R D Each is a saturated hydrocarbon group (eg, C 1-15 Alkyl, preferably C 1-6 (c3) The oxyethylene group (for example, a polyethylene glycol chain (PEG chain)) is the same as the oxyethylene group described in relation to the linker portion (linker-like hydrophilic portion) (c4).

[0114] R 1 ~R 9At least one of R may be a group for making the redox mediator compound positively charged. For example, in the case of a phenazine compound or a phenothiazine compound, in order to make the compound positively charged (cationic), R 1 ~R 9 (iv) an amino group which may have a substituent, preferably an unsubstituted amino group, which generates -NH3 in an aqueous solvent + (viii) a positively charged functional group such as a quaternary ammonium cation group (referred to as a "cationic functional group" in this specification).

[0115] When the cationic mediator (c) is a compound having a structure in which a redox mediator compound (c1) and a cationic polymer (c2) are bonded via a linker (c3) as required, R 1 ~R 9 At least one of the reactive groups may be a reactive group that is bondable to a group possessed by the cationic polymer (c2) or the linker (c3) used as required or the linker compound used to form it (referred to as "the specific reactive group of the redox mediator compound (c1)" in this specification, and sometimes simply referred to as "the specific reactive group" when it is obvious from the context that it refers to the redox mediator compound (c1).).

[0116] R 1 ~R 9 At least one of R may be other groups related to the performance as a redox mediator or groups related to the manufacture of the reagent layer. For example, in the case of phenazine compounds or phenothiazine compounds, in order to improve the hydrophilicity, 1 ~R 9 at least one of the following may have (iii) a hydroxyl group which may have a substituent, preferably an unsubstituted hydroxyl group; (iv) an amino group which may have a substituent, preferably an unsubstituted amino group; (viii) a functional group itself, such as a quaternary ammonium cationic group, which is called a so-called "hydrophilic group", or a hydrophilic group derived from such a hydrophilic group (preferably a hydrophilic group substituted with an (n)oxyethylene group or other hydrophilic group); or (v) a saturated or unsaturated hydrocarbon group which may have a substituent; (vi) an acyl group which may have a substituent; (vii) a phenyl group which may have a substituent, which becomes hydrophilic as a whole by having an (n)oxyethylene group or other hydrophilic group as a substituent, etc.

[0117] It should be noted that the so-called "hydrophilicity" in the present invention refers to the following property, that is, high affinity for water, and dissolving or miscible with water or other polar solvents, such as solvents used to react redox mediator compounds with cationic polymers when synthesizing cationic mediators, solvents used to dissolve cationic mediators when forming a given layer in an electrochemical sensor, etc., to the extent that the purpose can be achieved. As polar solvents, for example, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methyl-1-propanol, 2-methyl-2-propanol, formic acid, acetic acid, tetrahydrofuran, acetone, dioxane, methyl ethyl ketone, ethyl acetate, acetonitrile, dimethylformamide, and dimethyl sulfoxide can be cited.

[0118] (c2) Cationic polymer

[0119] “Cationic polymer” is a general term for polymers that have a positive charge as a net value of the polymer as a whole. The cationic polymer (c2) of the present invention can be any polymer as long as it has a structure capable of supporting the redox mediator compound (c1), that is, it has a group that can react with a group possessed by the redox mediator compound (c1) itself or a group possessed by the linker (c3) used as needed, and can be applied to a desired site, such as a working electrode, to form a reagent layer. The type of cationic polymer is not particularly limited, and any one type may be used alone, or two or more types may be used in combination.

[0120] Cationic polymers may be straight-chain, branched, comb-shaped, or any "chain structure", and the "chain structure" may contain one or more ring structures derived from cyclic compounds (aromatic hydrocarbon rings, non-aromatic hydrocarbon rings, aromatic heterocycles, non-aromatic heterocycles, etc.). The main chain and side chain of the cationic polymer (c2) are usually mainly composed of carbon atoms, and may contain at least one hetero atom selected from nitrogen atoms, oxygen atoms, and sulfur atoms. In other words, there may be ether bonds, thioether bonds, amide bonds, etc. containing hetero atoms in the middle. Cationic polymers (c2) usually have two or more (multiple) positively charged functional groups (cationic functional groups) in the side chain, and may further have cationic functional groups at one or both ends of the main chain. In addition, from the viewpoint that one molecule of the cationic polymer (c2) can carry two or more (plural) redox mediator compounds (c1) via a linker (c3) as required, the cationic polymer (c2) preferably has a reactive group having a bonding property with a group possessed by the redox mediator compound (c1) itself or a linker (c3) used as required or a group possessed by a linker compound used to form it (referred to as "specific reactive group of the cationic polymer (c2)" in this specification, and sometimes simply referred to as "specific reactive group" when it is obvious from the context that it refers to the cationic polymer (c2). In addition, one or both ends of the main chain may also have a specific reactive group. As a cationic polymer (c2) having a cationic functional group and a specific reactive group on a side chain and / or a terminal, various cationic polymers are known, and a cationic polymer having a desired property can be purchased, produced by changing an appropriate polymer, or synthesized using an appropriate monomer. The cationic polymer (c2) may be any of a homopolymer, a copolymer, and a polymer obtained by bonding and / or mixing these, and may be any of a random polymer, a block polymer, and a graft polymer.

[0121] Examples of cationic polymers (c2) include vinyl polymers, imine polymers, amino acid polymers, etc., which have cationic functional groups and specific reactive groups in the side chains (and at the ends). In addition, the following polymers are also included in the cationic polymers (c2), which can be called polymers with amino acids as monomers (however, as a concept, they are different from artificially synthesized amino acid polymers), proteins and polypeptides having natural amino acid sequences or altered (substituted, deleted, added, etc.) amino acid sequences, and having cationic functional groups and specific reactive groups in the side chains (and at the ends). Polysaccharide polymers that originally have or have been introduced with specific reactive groups and cationic functional groups are also included in the cationic polymers (c2).

[0122] Examples of ethylene polymers include homopolymers and copolymers synthesized from one or more monomers selected from monomers containing olefinic carbon-carbon double bonds capable of free radical polymerization, such as vinyl (CH2=CH-), allyl (CH2=CH-CH2-), acryloyl (CH2=CH-C(O)-), methacryloyl (CH2=C(CH3)-C(O)-), and the like, and their modifications (for example, polymers in which units derived from vinyl acetate have been vinylated by saponification, polymers treated to impart hydrophilicity, etc.). Examples of monomers containing olefinic carbon-carbon double bonds include ethylene, propylene, butadiene, isobutylene, tetrafluoroethylene, vinyl alcohol, vinyl acetate, vinyl chloride, vinylidene chloride, styrene, methylstyrene, allylamine, diallylamine, diallyldimethylammonium chloride, acrylic acid, methacrylic acid, methyl acrylate (also called methyl acrylate), methyl methacrylate (also called methyl methacrylate), butyl acrylate (also called butyl acrylate), butyl methacrylate (also called butyl methacrylate), hydroxyethyl methacrylate, acrylonitrile, etc. In addition, copolymers of methyl methacrylate and hydroxyethyl methacrylate, copolymers of butyl methacrylate and hydroxyethyl methacrylate, (meth)acrylic polymers such as poly(2-methacryloyloxyethylphosphorylcholine-co-n-butyl methacrylate), and polyester polymers such as polyethylene terephthalate, which are generally known as biocompatible polymers, can also be cited as preferred ethylene polymers.

[0123] As the ethylene polymer preferably used as the cationic polymer (c2), for example, polyallylamine hydrochloride, allylamine hydrochloride-diallylamine hydrochloride copolymer, allylamine-diallyldimethylammonium chloride copolymer, etc. can be cited. (Meth) acrylic acid polymers having quaternary ammonium cations, amino groups, etc. in the side chains (and ends) can also be cited as preferred ethylene polymers. More specifically, homopolymers or copolymers containing structural units derived from 2-aminoethyl methacrylate, (vinylbenzyl)trimethylammonium chloride, methacryloylcholine chloride, etc., poly(diallyldimethylammonium chloride), poly(allylamine hydrochloride), allylamine hydrochloride-diallylamine hydrochloride copolymer, allylamine-diallyldimethylammonium chloride copolymer, etc. can be preferably used as the cationic polymer (c2).

[0124] As an imine polymer, for example, poly(ethyleneimine) can be mentioned. Poly(ethyleneimine) has a structure such as -(CH2)2-NH2, -(CH2)2-NH-(CH2)2-NH2, -(CH2)2-N((CH2)2-NH2)2 in the side chain, and the amino group: -NH2 in the structure becomes a specific reactive group of the cationic polymer (c2), and can be bonded to a redox mediator compound (c1) or a linker (c3) having a corresponding appropriate specific reactive group (for example, a carboxyl group that has been actively esterified).

[0125] As amino acid polymers, for example, poly(L-lysine), poly(L-arginine), and poly(L-ornithine) can be cited. Poly(L-lysine) has a structure of -(CH2)4-NH2 in the side chain. Poly(L-arginine) has a structure of -(CH2)2-NH-C(=NH)-NH2 in the side chain. The amino group: -NH2 (or guanidine group: -NH-C(=NH)-NH2) contained in the side chain of these amino acid polymers becomes a specific reactive group of the cationic polymer (c2), and can be bonded to a redox mediator compound (c1) or a linker (c3) having a corresponding appropriate specific reactive group (for example, a carboxyl group that has been actively esterified). It should be noted that the amino acid polymer can form a salt like poly(L-arginine hydrochloride), for example.

[0126] Examples of polysaccharide polymers include cellulose derivatives such as chitosan. Chitosan is a polysaccharide obtained by hydrolyzing chitin and has an amino group in the side chain (in the sugar structure). The amino group or the like contained in the side chain of such a polysaccharide polymer becomes a specific reactive group of the cationic polymer (c2) and can be bonded to a redox mediator compound (c1) or a linker (c3) having a corresponding appropriate specific reactive group (e.g., an active esterified carboxyl group).

[0127] The degree of polymerization, weight average molecular weight, other properties, characteristics, etc. of the cationic polymer (c2) can be adjusted according to the embodiment and effect of the present invention and the type of cationic polymer (c2). The degree of polymerization of the cationic polymer (c2) is usually 100 or more. The average molecular weight of the cationic polymer (c2), typically the weight average molecular weight, is usually 10,000 or more, preferably 50,000 or more, and more preferably 100,000 or more. The upper limit of the weight average molecular weight of the cationic polymer (c2) is not particularly limited, but is usually less than 10,000,000, preferably less than 1,000,000.

[0128] It should be noted that the weight average molecular weight and molecular weight distribution of the cationic polymer (c2) can be measured by a known method depending on the type of the cationic polymer (c2), for example, gel permeation chromatography (GPC) can be used. In addition, when a commercially available product is purchased as the cationic polymer (c2), the value shown in its product catalog (for example, in the form of "Mw" or "MW") can be regarded as the weight average molecular weight.

[0129] (c3) Joint

[0130] The linker (c3) is a structure that exists as needed and is used to mediate the bonding between the redox mediator compound (c1) and the cationic polymer (c2). The linker (c3) is usually composed mainly of carbon atoms, excluding the reactive groups before the reaction or the bonding structure after the reaction at both ends, and is a site having a chain structure that can contain at least one hetero atom selected from nitrogen atoms, oxygen atoms and sulfur atoms. In other words, it is a site having a chain structure in which a bond containing a hetero atom such as an ether bond, a thioether bond, an amide bond, etc. may exist in the middle. The "chain structure" of the linker (c3) can be straight-chain or branched. In addition, the "chain structure" can contain one or more ring structures derived from cyclic compounds (aromatic hydrocarbon rings, non-aromatic hydrocarbon rings, aromatic heterocycles, non-aromatic heterocycles, etc.).

[0131] In one embodiment of the present invention, the linker (c3) also functions as a site (hydrophilic part) for improving the hydrophilicity of the cationic mediator (c), and may also be referred to as a "linker-like hydrophilic part". When the linker (c3) is a linker-like hydrophilic part, it is preferably a straight chain from the viewpoint of hydrophilicity and does not contain any ring structure derived from a cyclic compound.

[0132] In a preferred embodiment of the present invention, the linker-like hydrophilic portion comprises a hydrophilic portion having the formula: -(OC2H4) q - represents an oxyethylene group. In the formula, q represents, for example, an integer of 1 to 80, and preferably an integer of 3 to 36. It should be noted that among the oxyethylene chains represented by the formula, a chain in which q is large to a certain extent is generally called a "polyethylene glycol chain (PEG chain)" or the like.

[0133] In one embodiment of the present invention, the linker-like hydrophilic portion comprises a hydrophilic portion of the formula: -(CH2) p In one embodiment of the present invention, the main chain of the linker-like hydrophilic part comprises a hydrocarbon chain represented by the above formula: -(CH2) p - represents a hydrocarbon chain and the above formula: -(OC2H4) qp in the formula representing the hydrocarbon chain can be appropriately adjusted in consideration of the hydrophilicity of the hydrophilic part such as the linker so as to achieve a balance with q in the formula representing the oxyethylene chain.

[0134] The linker part (c3) may be derived from a compound (referred to as "linker compound" in the present specification) having at least two reactive groups (referred to as "specific reactive groups of linker compounds" in the present specification, and sometimes simply referred to as "specific reactive groups" when it is obvious from the context that it refers to linker compounds), wherein the at least two reactive groups are respectively bondable to the groups (specific reactive groups) possessed by the redox mediator compound (c1) and the groups (specific reactive groups) possessed by the cationic polymer (c2). For example, the linker compound is reacted with the redox mediator compound (c1), and then the linker compound in a state of being bonded to the redox mediator compound (c1) (in other words, "redox mediator compound (c1)-linker compound reactant") is reacted with the cationic polymer (c2), thereby generating a cationic mediator (c) which is a compound in which the redox mediator compound (c1) and the cationic polymer (c2) are bonded via the linker part (c3). In addition, the linker compound is reacted with the cationic polymer (c2), and then the linker compound in a state of being bonded to the cationic polymer (c2) (in other words, "cationic polymer (c2)-linker compound reactant") is reacted with the redox mediator compound (c1), thereby also generating a cationic mediator (c) which is a compound in which the redox mediator compound (c1) and the cationic polymer (c2) are bonded via the linker part (c3).

[0135] <Specific reactive groups>

[0136] As the specific reactive groups of the present invention, i.e., the specific reactive groups of the redox mediator compound (c1), the specific reactive groups of the cationic polymer (c2), and the specific reactive groups of the linker compound, various known reactive groups can be used, and various combinations can be used. The given reactive groups of the present invention can be bonded to each other by covalent bonds or by non-covalent bonds (e.g., electrostatic interactions). For example, from the viewpoint of the stability of the bonds, it is preferred to bond by covalent bonds.

[0137] The specific reactive groups of the present invention are preferably at least one selected from the group consisting of a carboxyl group or an active ester thereof, an amino group, a thiol group, a formyl group (aldehyde group), an epoxy group, and a maleimide group (referred to as a "preferred specific reactive group group" in this specification). It should be noted that the amino group, the thiol group, the formyl group (aldehyde group), the epoxy group, and the maleimide group as preferred specific reactive groups correspond to R in the general formulas (1) and (2) used as the redox mediator compound (c1).1 ~R 9 Substituents (iii) to (vii) may further have the substituents (c), (i), (j), (k) and (l) exemplified, and the carboxyl group and its active ester form correspond to the substituents (m') and (m), respectively. The groups that can react with each of the reactive groups contained in the preferred specific reactive group group are shown in Table 1. When the reactive group contained in the preferred specific reactive group group is selected as one of the specific reactive groups of the present invention, the group to react with may be another reactive group contained in the preferred specific reactive group group (the group marked with an underline in the table), or may be a reactive group not contained in the preferred specific reactive group group (the group not marked with an underline in the table, or the group not contained in the table).

[0138]

[0139] In a preferred embodiment of the present invention, any one of the specific reactive group of the redox mediator compound (c1) or the specific reactive group of the linker compound and the specific reactive group of the cationic polymer (c2) is the "reactive group A" in Table 1, and the other is the "reactive group B". Similarly, in a preferred embodiment of the present invention, any one of the specific reactive group of the redox mediator compound (c1) and the specific reactive group of the linker compound is the "reactive group A" in Table 1, and the other is the "reactive group B".

[0140] In a more preferred embodiment of the present invention, any one of the specific reactive group of the redox mediator compound (c1) or the specific reactive group of the linker compound and the specific reactive group of the cationic polymer (c2) is an amino group, and the other is a carboxyl group or an active ester thereof. Similarly, in a more preferred embodiment of the present invention, any one of the specific reactive group of the redox mediator compound (c1) and the specific reactive group of the linker compound is an amino group, and the other is a carboxyl group or an active ester thereof. For example, when using a redox mediator compound (c1) having an actively esterified carboxyl group as a specific reactive group; a linker compound having an amino group as a first specific reactive group and an actively esterified carboxyl group (for example, a carboxyl group actively esterified by NHS) as a second specific reactive group; and a cationic polymer (c2) having an amino group as a specific reactive group, firstly, a linker-like hydrophilic portion-introduced redox mediator compound is obtained by reacting the actively esterified carboxyl group of the redox mediator compound (c1) with the amino group of the linker compound (first amide bond), and then a cationic mediator (c) is obtained by reacting the actively esterified carboxyl group of the obtained linker-like hydrophilic portion-introduced redox mediator compound with the amino group of the cationic polymer (c2) (second amide bond).

[0141] The reagent layer of the present invention is typically a layer disposed on the working electrode in the electrochemical sensor of the present invention. The reagent layer may be any one or a combination of two or more (for example, two or more reagent layers having different compositions (types and / or contents) of the conductive carbon filler (a), the anionic dispersant (b), and the cationic mediator (c) may be stacked).

[0142] The reagent layer may contain a "redox enzyme" of a type corresponding to the analyte, such as in an electrochemical sensor in the form of a biosensor, or may not contain a redox enzyme, such as in the case of an electrochemical sensor other than a biosensor or a sensor other than an electrochemical sensor (such as an optical sensor).

[0143] The reagent layer may further contain components other than the conductive carbon filler (a), the anionic dispersant (b), and the cationic mediator (c) as necessary. Examples of such optional components include “oxidoreductase” (d).

[0144] (d) Oxidoreductase

[0145] Oxidoreductase (d) refers to an enzyme that can oxidize (including dehydrogenate) or reduce an analyte that is considered as an object of an electrochemical sensor, etc. The electrochemical sensor of the present invention typically adopts the form of an electrochemical sensor (biosensor) containing an oxidoreductase in a reagent layer, but is not limited to this, and may also adopt the form of an electrochemical sensor other than a biosensor that does not contain an oxidoreductase in the reagent layer, or a sensor other than an electrochemical sensor (such as an optical sensor). Whether the reagent layer contains an oxidoreductase (d) can be selected according to the purpose of the electrochemical sensor, etc., and which oxidoreductase (d) is included can be selected according to the type of analyte.

[0146] As oxidoreductase (d), for example, oxidase enzymes (glucose oxidase (Gox), lactate oxidase, pyruvate oxidase, cholesterol oxidase, amino acid oxidase, glutamate oxidase, fructosyl amino acid oxidase, alcohol oxidase, ascorbic acid oxidase, fructosyl peptide oxidase, bilirubin oxidase, aldehyde oxidase, etc.) and dehydrogenase enzymes (glucose dehydrogenase (GDH), lactate dehydrogenase, pyruvate dehydrogenase, amino acid dehydrogenase, glutamate dehydrogenase, 3-hydroxybutyrate dehydrogenase, alcohol dehydrogenase, aldehyde dehydrogenase) can be mentioned. Any one of the oxidoreductase (d) can be used alone, or two or more of them can be used in combination as needed.

[0147] In one embodiment of the present invention, the oxidoreductase (d) is a coenzyme-bound enzyme. As a coenzyme-reducing type oxidoreductase (d), for example, pyrroloquinoline quinone (PQQ)-bound GDH and flavin adenine dinucleotide (FAD)-bound GDH can be cited. In an embodiment in which glucose is used as the analyte, from the viewpoint of low reactivity to maltose that is not the analyte (for example, the enzyme activity for maltose when the enzyme activity for glucose is 100% can be set to 5% or less, preferably to 3% or less), FAD-bound GDH is preferred. As examples of FAD-bound GDH, enzymes from the genus Aspergillus (Aspergillus oryzae, Aspergillus terreus, etc.) and enzymes from the genus Mucor can be cited.

[0148] In one embodiment of the present invention, the oxidoreductase (d) can be cross-linked with a cationic mediator (c), in particular, a cationic polymer (c2) constituting the cationic mediator (c). For example, by using a cross-linking agent (e), the oxidoreductase (d) can be cross-linked with a cationic mediator (c), in particular, with a cationic polymer (c2). As a cross-linking agent (e), for example, glutaraldehyde can be cited. The cross-linking agent (e) reacts with a reactive group (e.g., an amino group) possessed by the oxidoreductase (d) as a protein, a reactive group possessed by the cationic mediator (c), and a reactive group (e.g., an amino group) possessed by the cationic polymer (c2) as a reactive group that does not react with the redox mediator compound (c1) or the linker (c2), or as a reactive group of a type different from the reactive group for reaction with the redox mediator compound (c1) or the linker (c2), respectively, thereby enabling the oxidoreductase (d) to be bonded to the cationic mediator (c) via the cross-linking agent (e). By utilizing such cross-linking to form a complex with a larger molecular weight, the outflow of the oxidoreductase (d) and the cationic mediator (c), especially the oxidoreductase compound (c1) constituting the cationic mediator (c) to the outside of the protective film can be further suppressed. It should be noted that, when a cross-linking agent (e) is used, the oxidoreductase (d) is sometimes bonded to each other through the cross-linking agent (e) by reacting with the reactive groups of each of the two molecules of the oxidoreductase (d). That is, when a cross-linking agent (e) is used, in the reagent layer, the oxidoreductase (d) can be cross-linked with the cationic mediator (c), especially with the cationic polymer (c2), while the oxidoreductase (d) can be cross-linked to each other.

[0149] ― Method for forming a reagent layer―

[0150] The method for forming a reagent layer of the present invention comprises at least the following step (1), and usually further comprises (2) and (3):

[0151] (1) a step of preparing a reagent solution containing a conductive carbon filler (a), an anionic dispersant (b), and a cationic mediator (c) (sometimes referred to as a "reagent solution preparation step" in this specification);

[0152] (2) A step of applying the reagent solution to the reagent layer formation site (sometimes referred to as "application step" in this specification);

[0153] (3) A step of drying the applied reagent solution to form a reagent layer (sometimes referred to as a "reagent layer forming step" in this specification).

[0154] (1) Reagent solution preparation process

[0155] The reagent solution preparation step (1) is a step of preparing a reagent solution containing main components constituting the reagent layer, namely, at least a conductive carbon filler (a), an anionic dispersant (b) and a cationic mediator (c), and may further contain other components, such as an oxidoreductase (d), a crosslinking agent (e), etc., as required.

[0156] The reagent solution can usually be prepared by adding the necessary components among the above components (a) to (e) to an aqueous solvent (water, or a mixed solvent of a solvent compatible with water and water). The aqueous solvent can be adjusted to have an appropriate pH by adding a pH adjuster, a buffer (liquid), other compounds, etc. as needed.

[0157] In one embodiment of the present invention, the pH of the reagent solution is 8.0 or less. By using a buffer solution in an amount that makes the pH of the reagent solution 8.0 or less, it is easy to exert the effect of improving the dispersibility of the conductive carbon filler (a). It should be noted that when the reagent solution contains an oxidoreductase (d), the pH of the reagent solution is preferably set to a range that maintains the activity of the oxidoreductase (d).

[0158] The pH of the reagent solution is usually adjusted using a buffer. Various buffers can be used as buffers, for example, acetate buffer (acetic acid and sodium acetate), phosphate buffer, citrate buffer, citrate phosphate buffer, Tris buffer (trishydroxymethylaminomethane, also known as tromethamine), Bis-Tris buffer (bis(2-hydroxyethyl)iminotris(hydroxymethyl)methane), HEPES buffer (2-[4-(2-hydroxyethyl)-1-piperazinyl]ethanesulfonic acid), MES (2-morpholinoethanesulfonic acid monohydrate), MOPS (3-morpholinopropanesulfonic acid), PBS (phosphate buffered saline, usually sodium chloride, potassium chloride, disodium hydrogen phosphate and potassium dihydrogen phosphate), etc. By using an appropriate buffer (buffer), the pH of the reagent can be set to the desired value (range).

[0159] In one embodiment of the present invention, the concentration of metal ions in the reagent solution is 200mM or less. When the concentration of metal ions in the reagent solution is high, some types of metal ions will hinder the dispersibility of the conductive carbon filler, and agglomeration may occur, so there is a tendency that the concentration of metal ions in the reagent solution is lower. In the case of using a compound (buffer) containing metal ions or a buffer prepared therefrom to adjust the pH of the reagent solution, the concentration of metal ions in the reagent solution is calculated based on the amount of the buffer or the buffer required to set the desired pH, and it is preferred to select a buffer or buffer that can be made into 200mM or less, or conversely, it is preferred to select a buffer or buffer that can be made into 200mM or less. In the case of using a compound (buffer) that does not contain metal ions or a buffer prepared therefrom, the concentration of metal ions in the reagent solution can naturally be set to 200mM or less. Regarding the concentration of metal ions in the reagent solution, when the metal salt is an alkali metal ion, it is preferably set to less than 100mM, for example, to 80mM or less.

[0160] Since the metal ions in the reagent solution are derived from various substances used in the preparation of the reagent solution, the composition of the reagent solution, the types and amounts of each component, etc. can be adjusted so that the concentration of the metal ions is within an appropriate range. For example, since the metal ions in the reagent solution are sometimes derived from a buffer solution, it is sufficient to set the composition of the buffer solution used to adjust the pH of the reagent solution (the types and concentrations of the compounds contained in the buffer solution) to an appropriate composition. In addition, since there are cases where the metal ions in the reagent solution are derived from a substance that forms a salt as an anionic dispersant (b), it is sufficient to take into account the amount of the anionic dispersant (b) that forms such a salt as needed.

[0161] The order of adding the components contained in the reagent solution can be adjusted appropriately, and for example, it is preferable to carry out the addition in the order of the following steps (1-1) and (1-2).

[0162] (1-1) A step of dispersing the conductive carbon filler (a) in an aqueous solution containing at least an anionic dispersant (b) to obtain a dispersion.

[0163] (1-2) A step of adding a cationic mediator (c) to the obtained dispersion to obtain a reagent solution.

[0164] The concentrations of the conductive carbon filler (a), the anionic dispersant (b), the cationic mediator (c), and the oxidoreductase (d) used as required, or the ratio of their concentrations in the reagent solution can be appropriately adjusted in consideration of the embodiment, effect, etc. of the present invention.

[0165] The concentration of the conductive carbon filler (a) in the reagent solution is, for example, in the range of 0.1 to 30 w / v% (mg / mL).

[0166] The concentration of the anionic dispersant (b) in the reagent solution is, for example, in the range of 0.01 to 30 w / v% (mg / mL).

[0167] In the reagent solution preparation step (1), a treatment for improving the dispersibility of the conductive carbon filler (a) in the reagent solution (sometimes referred to as "dispersion treatment" in this specification) may be performed by applying physical energy to the reagent solution. The dispersion treatment may be performed, for example, between the above steps (1-1) and the above step (1-2), or may be performed after the above step (1-2) (before the next application step (2)) instead of or in addition to the above step (1-2).

[0168] The means (method and conditions thereof, apparatus used, etc.) for applying "physical energy" are not particularly limited as long as they can improve the dispersibility of the conductive carbon filler (a) in the reagent solution. In a representative embodiment of the present invention, ultrasonic treatment is used as the above-mentioned means, but other means may also be used. The conditions (output power, time, etc.) of the ultrasonic treatment can be appropriately adjusted. The apparatus for ultrasonic treatment can also be appropriately selected, for example, an ultrasonic homogenizer can be used.

[0169] The oxidoreductase (d) is preferably added at the stage where the dispersion treatment is completed in the reagent solution preparation step (1) so as not to be affected by physical energy. The cross-linking agent (e), such as glutaraldehyde, for cross-linking the oxidoreductase (d) and the cationic mediator (c) or for cross-linking the oxidoreductases (d) is preferably added after the oxidoreductase (d) is added.

[0170] In addition, when a compound in which a redox mediator compound (c1) and a cationic polymer (c2) are bonded via a linker (c3) as required is used as the cationic mediator (c), the cationic mediator (c) is preferably added after optimizing the dispersibility of the conductive carbon filler (a) by applying physical energy to the reagent solution through a dispersion treatment such as ultrasonic treatment.

[0171] (2) Application process

[0172] The applying step (2) is a step of applying (dropping, coating, etc.) the reagent solution obtained in the reagent solution preparing step (1) to the reagent layer forming site, for example, at least a part of the working electrode.

[0173] The means for "application" (method and conditions thereof, apparatus used, etc.) are not particularly limited as long as the reagent layer can be formed from the reagent solution, and the means for applying the reagent solution in the conventional method for forming a reagent layer (or the method for manufacturing an electrochemical sensor) can be adopted. In a representative embodiment of the present invention, an appropriate amount of the reagent solution obtained by the reagent solution preparation step (1) is dripped onto at least a portion of the working electrode (the portion forming the reagent layer), thereby performing the application step. The area to be applied and the amount of the reagent solution can be adjusted according to the thickness of the target reagent layer.

[0174] (3) Reagent layer formation process

[0175] The reagent layer forming step (4) is a step of drying the reagent solution applied to the reagent layer forming site (eg, at least a portion of the working electrode) in the applying step (2) to form a coating layer.

[0176] The means for "drying" (method and conditions, apparatus used, etc.) are not particularly limited as long as a (preferably uniform) reagent layer can be formed from the applied reagent solution, and means according to the reagent solution drying process in the manufacture of conventional electrochemical sensors can be used. In a representative embodiment of the present invention, the working electrode to which the reagent solution is applied is left to stand at room temperature, thereby performing a reagent layer forming process to form a reagent layer.

[0177] ― Electrochemical Sensors ―

[0178] The electrochemical sensor for detecting or quantifying an analyte of the present invention comprises a working electrode, a counter electrode, and the reagent layer of the present invention as described above disposed on the working electrode, and further comprises a protective film covering at least the reagent layer as necessary.

[0179] The "protective film" is a film-like member used to prevent or inhibit the leakage of substances (conductive carbon filler (a), cationic mediator (c), oxidoreductase (d) used as needed, etc.) contained in the reagent layer to the environment outside the protective film (in vivo, culture medium, etc.). It is appropriate that the protective film covering the reagent layer has a hole that can be penetrated in the protective film so that the analyte present in the environment outside the protective film can contact the reagent layer. Such a protective film is preferably formed when the electrochemical sensor is used for continuous measurement, and may not be formed when the electrochemical sensor is used for a single run measurement.

[0180] Since the working electrode (probe having the working electrode) formed with the reagent layer is used after being inserted into a living body or immersed in a culture medium, the protective film covering the surface thereof has biocompatibility that proteins and cells are not adsorbed or are difficult to be adsorbed, and is usually preferably formed of a biocompatible polymer having such a property. Examples of the biocompatible polymer include copolymers of methyl methacrylate and hydroxyethyl methacrylate, copolymers of butyl methacrylate and hydroxyethyl methacrylate, and poly(2-methacryloyloxyethylphosphorylcholine-co-n-butyl methacrylate).

[0181] The protective film can be formed by preparing a solution containing a raw material for forming the protective film (protective film solution), immersing the area where the protective film is to be formed, for example, at least the area of ​​the working electrode where the reagent layer is formed, pulling it up and then drying it, and repeating this process multiple times as needed.

[0182] The electrochemical sensor of the present invention may further include a reference electrode as required. That is, the electrochemical sensor of the present invention may be a two-electrode type consisting of a working electrode and a counter electrode, or a three-electrode type consisting of a working electrode, a counter electrode, and a reference electrode.

[0183] In one embodiment of the present invention, the electrochemical sensor can be manufactured as an implantable electrochemical sensor, for example, it can be manufactured as a biosensor for CGM (Continuous Glucose Monitoring) for self-blood glucose measurement that continuously or semi-continuously measures the glucose concentration in the blood or interstitial fluid, for example, over a period of several days to several weeks. On the other hand, in one embodiment of the present invention, the electrochemical sensor can also be manufactured as a non-implantable electrochemical sensor, for example, it can also be manufactured as a biosensor for continuously or semi-continuously measuring the concentration of glucose, etc. in a culture medium.

[0184] Hereinafter, an embodiment of the electrochemical sensor of the present invention when it is an implantable type will be described with reference to the accompanying drawings. However, the accompanying drawings and the following description are illustrative, and the technical scope of the present invention is not limited to the embodiments disclosed by them, and it should be understood that the embodiments with various modifications are included within the scope that can solve the problems of the present invention and within the scope that can exert the effects of the present invention.

[0185] In the following description, the Figure 1 (A) and (B), Figure 3 as well as Figure 7 The paper front direction, Figure 2 (A) to (C) and Figures 4 to 6 The surface on the paper that is upward is called the "upper surface". Figure 1 (A) and (B), Figure 3 as well as Figure 7 The paper depth direction, Figure 2 (A) to (C) and Figures 4 to 6 The surface below the paper is called the "lower surface". Figure 1 (A) and (B), Figure 2 (A)~(C), Figure 5 to Figure 7 In either direction of the paper, and Figure 4 The side of the paper that is closer to the front or the back is called the "side". Figure 1 The dimension in the vertical direction of the paper surface of (A), that is, the dimension in the direction parallel to the arrow X2 indicating the insertion direction of the sensor into the living body, and Figure 3 and Figure 7 The vertical dimension of the paper is called "length". Figure 1 The dimension in the left-right direction of the paper surface of (A), that is, the dimension in the direction perpendicular to the arrow X2, and Figure 3 and Figure 7 The vertical dimension of the paper is called "width".

[0186] Figure 1 It is a top view of the sensor 11 according to one embodiment of the present invention. Figure 1 (A) shows the entire sensor 11 . Figure 1 (B) Figure 1 (A) shows an enlarged view of the front end portion (sensing portion) of the sensor 11. The sensor 11 is suitable for constructing a system of an implantable biosensor worn on a living body for self-monitoring of blood sugar levels, and the sensor 11 in this case can be inserted into the living body as a protruding portion (probe) protruding from a main body (not shown). In addition, the sensor 11 can also be used, for example, when constructing a system for measuring the concentration of an analyte in a culture medium.

[0187] Figure 1 The region X1 (head) of the sensor 11 shown in (A) is housed in the main body (not shown), and the front end portion (sensing portion) of the sensor 11 protrudes from the main body. Arrow X2 indicates the insertion direction when the sensor 11 is inserted into the biological body. Regarding the size of the sensing portion, the length is, for example, 20 to 3 mm, preferably 10 to 3 mm, and the width is, for example, 1 to 50 μm, preferably 500 to 50 μm.

[0188] Figure 1In the sensor 11, the sensor 11 has a substrate 21, an electrode 22, a reagent layer 23, a silver / silver chloride layer (sometimes also referred to as a reference layer) 24 and a membrane 25. The electrode 22 is formed on the substrate 21 as usual, and includes a working electrode 22a, a reference electrode 22b and a counter electrode 22c. The working electrode 22a and the reference electrode 22b are physically and electrically separated by the groove A1, and the reference electrode 22b and the counter electrode 22c are physically and electrically separated by the groove A2. The reagent layer 23 is formed on the working electrode 22a. The silver / silver chloride layer 24 is formed on the reference electrode 22b. The membrane 25 covers the upper surface of the sensor 11 except for a part of the electrode 22 (the part of the region X4 in the region X1 of the head, the part of the region X3 of the counter electrode 22c, etc.) and a part of the reagent layer 23 (by having an opening to expose them). It should be noted that the exposed region X4 of the electrode 22 is connected to the circuit of the main body 11.

[0189] It should be noted that if Figure 1 As shown in the region X5 of (B), it is preferred that the reagent layer 23 is not formed at the front end (from the front end to a given distance) of the sensor 11. In other words, it is preferred that the reagent layer 23 is formed at a distance from the front end of the sensor 11. This is because, by setting it in this way, when the sensor 11 is inserted into the living body, it is possible to suppress the reagent layer 23 from being peeled off (rolled up) from the sensor 11.

[0190] Figure 2 (A) Yes Figure 1 (B) is a cross-sectional view taken along the AA line. In the portion of the sensor 11 where the reagent layer 23 is formed, the substrate 21, the electrode 22 (working electrode 22a), and the reagent layer 23 are stacked in this order. In the portions 11a and 11b, the electrode 22 (working electrode 22a), the reagent layer 23, and the membrane 25 are not stacked (are trimmed), and the substrate 21 is exposed.

[0191] Figure 2 (B) Yes Figure 1 (B) is a cross-sectional view taken along the arrow BB. In the portion on the right side relative to the groove A1 where the silver / silver chloride layer 24 is formed, the substrate 21, the electrode 22 (reference electrode 22b), the silver / silver chloride layer 24, and the film 25 are stacked. In the portion on the left side relative to the groove A1 that is physically and electrically separated from the reference electrode 22b, the substrate 21, the electrode 22 (working electrode 22a), and the film 25 are stacked. The side surface of the silver / silver chloride layer 24 ( Figure 2 (B) The right side surface) is exposed without the film 25. In the present embodiment, the upper surface of the silver / silver chloride layer 24 is covered with the film 25, but it may be exposed without being covered with the film 25.

[0192] Figure 2 (C) Yes Figure 1(B) CC cross-sectional view. The substrate 21 and the electrode 22 (counter electrode 22c) are stacked in the portion on the right side relative to the groove A2. The upper surface of the counter electrode 22c is not covered by the film 25 and is exposed. The substrate 21, the electrode 22 (reference electrode 22b) and the film 25 are stacked in the portion sandwiched by the groove A1 and the groove A2. The substrate 21, the electrode 22 (working electrode 22a) and the film 25 are stacked in the portion on the left side of the groove A1.

[0193] The substrate 21 is typically a sheet of synthetic resin. The material of the substrate 21 is not particularly limited as long as it is a resin material such as a plastic material (synthetic resin) having at least one of the characteristics of flexibility, easy processing, and heat resistance. As a representative example of the resin material of such a substrate 21, polyethylene terephthalate (PET) can be cited, and other general-purpose plastics such as polyethylene, polypropylene, and polyethylene naphthalate can also be cited. In addition, when high heat resistance is required, polyimide is preferably used.

[0194] The electrode 22 is a thin film (thin layer) formed on the substrate 21. The material of the electrode 22 is not particularly limited as long as it is a metal or carbon material having conductivity and stability (for example, oxidation resistance or salt resistance). Representative examples of the material of such an electrode 22 include gold, platinum, palladium, carbon, etc. It should be noted that when the working electrode 22a (reagent layer 23) is formed on one of the upper surface and the lower surface of the sensor 11 and the counter electrode 22c is formed on the other, different electrode materials can be used.

[0195] A potential (a potential based on the reference electrode 22b) sufficient to oxidize the mediator reduced by the reaction of the analyte (e.g., glucose) by the redox enzyme is applied to the working electrode 22a. The glucose concentration is measured by monitoring the current flowing between the working electrode 22a and the counter electrode 22c. The reagent layer 23 is formed on the upper surface of the working electrode 22a at the front end portion of the sensor 11.

[0196] A silver / silver chloride layer 24 is formed on the upper surface of the reference electrode 22b at the front end of the sensor 11 as needed. In the present embodiment, in order to achieve a more accurate measurement, an example of a three-electrode structure consisting of a working electrode 22a, a reference electrode 22b, and a counter electrode 23c is given, but it is also possible to not include the reference electrode 22b and to set it as a two-electrode structure consisting of a working electrode 22a and a counter electrode 23c (for example, such a two-electrode structure is the mainstream in the currently commercially available SMBG (self-monitoring blood glucose meter)). In addition to being a silver / silver chloride electrode formed with a silver / silver chloride (Ag / AgCl) layer 24 as shown in the present embodiment, the reference electrode can also be an electrode formed with a layer containing mercury, such as a hydrogen electrode, a calomel electrode, etc.

[0197] The film 25 is an insulating sheet-like member formed (laminated) on a given portion of the electrodes 22 (working electrode 22a, reference electrode 22b, and counter electrode 22c) formed on the substrate 21 and the silver / silver chloride layer 24. The thickness of the film 25 is usually 1 μm or more and 150 μm or less, preferably 3 μm or more and 50 μm or less, and more preferably 5 μm or more and 30 μm or less. The film 25 has openings in a portion corresponding to the reagent layer 23 located at the front end of the sensor 11 and a portion corresponding to a portion of the counter electrode 22c, and the reagent layer 23 and the counter electrode 22c in this portion are exposed.

[0198] The film 25 may be, for example, a film in which an adhesive sheet (e.g., acrylic, rubber, or hot melt) is attached to a sheet of the same resin material as the substrate 21. The sheet of the resin material may be a sheet of the same resin material as the substrate 21, or a sheet of a resin material different from the substrate 21. The adhesive sheet alone may be used as the film 25. A heat or photoplasticized resist film or a layer formed of a resist ink may be used as the film 25.

[0199] The reagent solution for forming the reagent layer 23 is applied by dripping from the opening of the corresponding portion of the membrane 25 onto the surface of the electrode 22 (working electrode 22a). From the viewpoint of operability of such a process, it is preferred that the contact angle (α) of the reagent solution with respect to the surface of the membrane 25 is greater than the contact angle (β) of the reagent solution with respect to the opening of the membrane 25, that is, the surface of the exposed working electrode 22a, and the larger the difference (α-β), the more preferred. For example, it is preferred that α is greater than or equal to 90° and β is less than or equal to 50°. It should be noted that the "contact angle" referred to here is a "static contact angle" measured by the "θ / 2 method". Even if the material itself forming the membrane 25 and / or the material itself forming the exposed working electrode 22a does not satisfy the above-mentioned contact angle conditions, the above-mentioned contact angle conditions can be satisfied by appropriate surface treatment, for example, by performing at least one of a hydrophobic treatment on the membrane 25 and a hydrophilic treatment on the working electrode 22a.

[0200] Although in Figure 1 Although not shown in (A) and (B), at least the portion of the sensor 11 including the reagent layer 23 may be covered with a protective film. Figure 2 A protective film is formed (laminated) on the upper surface of the reagent layer 23 of (B). Figures 4 to 6 will be described later at the same time.

[0201] The method for manufacturing the sensor 11 is not particularly limited, and any method that can manufacture the sensor 11 having the above-described structure at a given location can be appropriately selected and used. For example, the sensor 11 can be manufactured by performing the following steps (i) to (viii):

[0202] (i) a step of forming (stacking) the electrode 22 on the upper surface of the substrate 21;

[0203] (ii) forming grooves A1 and A2, wherein the grooves A1 and A2 physically and electrically separate the electrode 22 into three regions: a working electrode 22a, a reference electrode 22b, and a counter electrode 22c;

[0204] (iii) forming a silver / silver chloride layer 24 on the upper surface of the electrode 22 (reference electrode 22 b );

[0205] (iv) forming (laminating) a film 25 on the upper surfaces of the electrode 22 and the silver / silver chloride layer 24;

[0206] (v) forming a reagent layer 23 on the upper surface of the electrode 22 (working electrode 22 a );

[0207] (vi) a step of removing the reagent layer 23 and a portion of the electrode 22 (region X6);

[0208] (vii) a step of cutting the sensor 11 from the substrate 21 ;

[0209] (viii) A step of forming a protective film.

[0210] Regarding the above-mentioned step (i), the method for forming (stacking) the electrode 22 can be appropriately selected and adjusted in consideration of the combination of the material of the electrode 22 and the material of the substrate 21. For example, when the material of the substrate 21 is a synthetic resin such as PET and the material of the electrode 22 is a metal, the electrode 22 composed of the metal material can be formed on the surface of the substrate 21 by evaporation (including sputtering). However, in addition to this, printing, plating, spin coating, etc. can also be used. When the material of the substrate 21 is a synthetic resin such as PET and the material of the electrode 22 is carbon, for example, the electrode 22 composed of carbon can be formed by printing carbon paste on the surface of the substrate 21. It should be noted that the substrate 21 in this step does not need to have the shape of the sensor 11 in advance. In order to be able to cut out the sensor 11 by the subsequent step (vii), a substrate 21 having a larger size than the sensor 11 can be used.

[0211] Regarding the above step (ii), as a means for forming the grooves A1 and A2 , for example, laser trimming can be used.

[0212] Regarding the above-mentioned step (iii), the method for forming the silver / silver chloride layer 24 can be appropriately selected and adjusted in consideration of the combination of the material of the silver / silver chloride layer 24 and the material of the electrode 22. For example, a silver / silver chloride paste (ink) is used, and after printing or coating the upper surface of the electrode 22 made of metal or carbon by screen printing, inkjet method, etc., and then drying, the silver / silver chloride layer 24 can be formed on the upper surface of the electrode 22. Alternatively, the silver / silver chloride layer 24 can be formed by printing, coating, plating, etc. with silver (Ag) on ​​the upper surface of the electrode 22, and then chlorinating the surface.

[0213] Regarding the above-mentioned step (iv), the method for forming (stacking) the film 25 can be appropriately selected and adjusted in consideration of the combination of the material of the film 25 and the material of the electrode 22 and the silver / silver chloride layer 24. For example, an opening corresponding to the size of the reagent layer 23 (at least larger than the size of the reagent layer 23) is formed in the film 25 composed of a laminate of a resin sheet and an adhesive sheet, or composed of an adhesive sheet alone. Such a film 25 is arranged on the upper surface of the electrode 22 so that its opening surrounds the portion of the electrode 22 (working electrode 22a) where the reagent layer 23 is formed, and is fixed by an adhesive sheet. On the other hand, a film 25 having a given opening can also be formed (stacking) by removing a portion of a given position and size as described above using a resist film or resist ink.

[0214] It should be noted that the film 25 is not formed on the upper surface of a portion (region X3) of the counter electrode 22c in the electrode 22, and the counter electrode 22c is exposed. Therefore, for example, after temporarily forming a film including the upper surface of the counter electrode 22c as described above, a notch-shaped opening may be formed in the film 25 by cutting or the like.

[0215] In the above step (v), for example, a membrane 25 having a predetermined opening and a pre-prepared reagent solution are used, and the reagent solution is dropped into the opening of the membrane 25 formed (laminated) in the above step (iv), thereby applying the reagent solution to at least a portion of the working electrode 22a. Thereafter, the applied reagent solution is dried, thereby forming a reagent layer 23 on the upper surface of the working electrode 22a.

[0216] It should be noted that the opening of the membrane 25 may have a shape that forms a ratio sensor 11 ( Figure 1 In this case, the reagent layer formed by the applied reagent solution and being larger than the width of the sensor 11 is shaped by the following step (vi) to have a given width and shape.

[0217] At the end of the sensor 11 (front end) in the width direction, the reagent layer 23 and the electrode 22 in the above step (vi) are removed (trimmed) over a given length in the longitudinal direction of the sensor 11 (for example, the insertion direction into the biological body). After the reagent layer is formed in a certain area by trimming in such a step (vi), an appropriate portion (preferably a uniform portion) is selected to form a reagent layer of a given area uniform between the sensors, and in the following step (vii), the sensor 11 is cut out from the substrate 21 along the outer shape without cutting the formed reagent layer. The method of removing the reagent layer 23 and the electrode 22 can be appropriately selected and adjusted in consideration of the material of the reagent layer 23 (the composition of the reagent solution) and the material of the electrode 22. For example, the reagent layer 23 and the electrode 22 can be removed by laser trimming.

[0218] Regarding the above step (vii), the method of cutting (cutting) the sensor 11 from the substrate 21 can be appropriately selected and adjusted in consideration of the material of the substrate 21 , the shape of the cut sensor, etc. For example, when the material of the substrate 21 is resin, a common cutting technique can be used.

[0219] The cutting position includes the portion trimmed in step (vi), and for example, the cutting position may be near the center line of the bottom of the concave portion trimmed by laser. In other words, the cutting is performed at a position slightly away from the trimmed reagent layer 23 and the working electrode 22 a.

[0220] In addition to referring to the method for forming the protective film described in the context of the electrochemical sensor of the present invention, the above step (viii) can be appropriately selected and adjusted in consideration of the material of the protective film, i.e., the composition of the protective film solution, the combination of the material of the coated portion (mainly, the material of the reagent layer 23, i.e., the composition of the reagent solution), the shape and area of ​​the coated portion, etc. For example, the working electrode 22a (at least the portion where the reagent layer 23 is formed) is immersed in the protective film solution, pulled up, and then dried, so that the portion can be coated with the protective film.

[0221] Figure 3 1 is a top view of a sensor 101 according to another embodiment of the present invention. The sensor 101 is composed of a sensing portion (a distal end portion inserted into a living body or immersed in a culture medium) 121 and a terminal portion 122 for electrically connecting to an internal circuit of a body (not shown).

[0222] Figure 4 express Figure 3A cross-sectional view of the sensor 101 at the A-A' cutting line. Conductive thin films 112 are provided on both surfaces of an insulating substrate 111. The conductive thin film 112 on one surface (front side) of the insulating substrate 111 is formed with grooves 113 reaching the surface of the insulating substrate 111 by laser drawing, and is electrically insulated, thereby being separated into a working electrode region 112a and a reference electrode region 112b.

[0223] The upper surface of the insulating substrate 111 is covered with an insulating resist film 116a having an opening for forming a reference electrode 115 at a predetermined position of the reference electrode region 112b, and the lower surface of the insulating substrate 111 is covered with an insulating resist film 116b. On the other hand, from the end of the sensing portion 121 to a portion at a certain distance, the upper and lower surfaces are not covered with the insulating resist films 116a and 116b, and the area 112a on the front side becomes the working electrode 114, and the area 112c on the back side becomes the counter electrode 117. The reagent layer 118 is formed on the working electrode 114.

[0224] Figure 5 express Figure 4 The cross-sectional view at the B-B' cutting line in the figure is as follows: Figure 6 express Figure 4 The cross-sectional view at the C-C' cutting line in FIG. Figure 5 As shown, at the BB' cutting line, a protective film 119, a reagent layer 118, a working electrode 114, an insulating substrate 111, a counter electrode 117 and a protective film 119 are formed in order from the upper surface to the lower surface (in the direction of the arrow in the figure). Figure 6 As shown, at the CC' cutting line, a protective film 119, a reference electrode 115 (insulating resist film 116a), a working electrode region 112a, an insulating substrate 111, a counter electrode region 112c, an insulating resist film 116b and a protective film 119 are formed in sequence from the upper surface to the lower surface (in the direction of the arrow in the figure). It should be noted that Figure 6 The working electrode region 112 a and the counter electrode region 112 c shown in the figure have insulating resist films 116 a and 116 b on their upper surfaces, and therefore do not function as working electrodes and counter electrodes.

[0225] Figure 72 is a top view of a sensor 201 according to another embodiment of the present invention. The sensor 201 includes a sensing portion 202 having a structure for electrochemically measuring an analyte, a terminal portion 203 having a structure for electrically connecting to an internal circuit of a main body (not shown), and a notch portion 204 provided near the terminal portion. The sensor 201 is, for example, an embodiment suitable for constructing a system for measuring an analyte in a culture medium, the sensing portion 202 having a structure that can be immersed in a culture medium with a small amount of liquid, and the notch portion 204 having a structure suitable for installing the sensor 201 in a culture container. Figure 7 (A) shows an electrode pattern before forming a film (insulating resist film) 230 , Figure 7 (B) shows the electrode pattern after the film 230 is formed.

[0226] like Figure 7 As shown in (A), the sensor 201 has electrodes 220 formed on a substrate 210, and the electrodes 220 are physically and electrically separated into a first working electrode 221, a second working electrode 222, a reference electrode 223, and a counter electrode 224 by a groove 225. Figure 7 As shown in (B), the first working electrode 221 has an exposed area 221a at the sensing portion 202 and an exposed area 221b at the terminal portion 203 by being covered with a film 230. Similarly, the second working electrode 222, the reference electrode 223, and the counter electrode 224 also have exposed areas 222a, 223a, and 224a at the sensing portion 202 and exposed areas 222b, 223b, and 224b at the terminal portion 203, respectively. In the sensing portion 202, the exposed area 221a of the first working electrode and the exposed area 222a of the second working electrode are arranged in a horizontal arrangement to maximize the area, and the exposed area 223a of the reference electrode and the exposed area 224a of the counter electrode are also arranged. Different types of reagent layers (not shown) for measuring different analytes can be formed in the exposed area 221a of the first working electrode and the exposed area 222a of the second working electrode. The exposed regions 221 b , 222 b , 223 b , and 224 b of the terminal portions 203 of the first working electrode, the second working electrode, the reference electrode, and the counter electrode can be electrically connected to a main body (not shown) by, for example, electrode pads (not shown).

[0227] Example

[0228] The materials used in the present examples (including test examples) are as follows.

[0229] (a) Conductive carbon filler

[0230] (a-1) Carbon black…Sigma-Aldrich “05-1530”

[0231] (b) Anionic dispersants

[0232] (b-1A) Poly(acrylic acid) 100000…Sigma-Aldrich “523925”, Average Mw~100000

[0233] (b-1B) Poly(acrylic acid) 25000…Fujifilm Wako Pure Chemical Industries, Ltd. “162-18581”, average molecular weight: about 25000

[0234] (b-1C) Poly(acrylic acid) 5000…Fujifilm Wako Pure Chemical Industries, Ltd. “165-18571”, average molecular weight: about 5000

[0235] (b-2A) Poly(styrene sulfonate sodium salt)…Sigma-Aldrich “81609”, Average Mw~16800

[0236] (b-2B) Poly(sodium 4-styrene sulfonate)…Sigma-Aldrich “243051”, Average Mw~70000

[0237] (b-3) Poly(4-styrenesulfonic acid-co-maleic acid) sodium salt…Sigma-Aldrich “434558”, Average Mw~20000

[0238] (b-4) Poly(ethylene oxide)-b-poly(acrylic acid)…Polymer Source “P6348-EOAA”, Mn (POA-b-PAA): 2-b-2.4 (10 3 g / mol)

[0239] (b-5) Poly(styrene)-b-poly(acrylic acid)…Polymer Source “P2397-SAA”, Mn (PS-b-PAA): 1.5-b-44 (10 3 g / mol)

[0240] (non-b) non-anionic dispersants

[0241] (Non-b-1) Hydroxypropyl cellulose… Nippon Soda Co., Ltd. “NISSO HPC”

[0242] (c) Cationic mediators

[0243] (c-1) Polymer-bonded PNT1 ... has a structure in which a phenothiazine compound NHS body (PNT-70) as a redox mediator compound (c1) is bonded to a copolymer of 2-aminoethyl methacrylate hydrochloride, (4-vinylphenyl)methanamine and methacryloylcholine chloride (hereinafter referred to as "polymer C") as a cationic polymer (c2).

[0244] (c-2) Polymer-bonded PNT2 ... has a structure in which a phenothiazine compound (PNT-70) as a redox mediator compound (c1) and poly(L-lysine) hydrochloride (ALAMANDA POLYMERS "PLKC800") (hereinafter referred to as "PLL") as a cationic polymer (c2) are bonded.

[0245] The synthesis methods of the above-mentioned PNT-70, polymer C, polymer-bonded PNT1, and polymer-bonded PNT2 are respectively as follows.

[0246] [Synthesis Example 1] Synthesis of PNT-70

[0247] (1) Synthesis of sulfonic acid fragment

[0248]

[0249] The sulfonic acid fragment was synthesized using the above reaction.

[0250] (2) Synthesis of sulfonic acid fragment

[0251]

[0252] The carboxylic acid fragment was synthesized by the two-step reaction in acetonitrile and tetrahydrofuran (THF) as described above.

[0253] (3) Synthesis of PNT-34

[0254]

[0255] The sulfonic acid fragment and carboxylic acid fragment synthesized as described above were suspended in MeOH / H2O, and 50% Ag2CO3 / diatomaceous earth was added in batches over 15 minutes at an internal temperature of about 47°C. After the addition, the mixture was stirred at an internal temperature of about 68°C for 2.5 hours. After cooling to room temperature naturally, the mixture was filtered through diatomaceous earth and the filtrate was concentrated. The residue was purified several times by silica gel column chromatography to obtain PNT-34.

[0256] (4) Synthesis of condensation product (PNT-68)

[0257] [Chemistry 6]

[0258]

[0259] Under an Ar atmosphere, PNT-34 was dissolved in dichloromethane, and amino-PEG12-tert-butyl ester and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI·HCl) were added, followed by stirring at room temperature for 3 hours. The reaction solution was concentrated and purified three times by silica gel column chromatography to obtain a condensate (PNT-68).

[0260] (5) Synthesis of deprotected product (PNT-69)

[0261] [Chemistry 7]

[0262]

[0263] The condensate (PNT-68) obtained in (4) was dissolved in dichloromethane, trifluoroacetic acid (TFA) was added, and the mixture was stirred at room temperature for 3 hours. The reaction solution was concentrated and azeotroped with toluene several times to obtain a deprotected product (PNT-69).

[0264] (6) Synthesis of PNT-69NHS (PNT-70)

[0265] [Chemistry 8]

[0266]

[0267] The deprotected product (PNT-69) was dissolved in dichloromethane, and N-hydroxysuccinimide (NHS) and EDCI·HCl were added, followed by stirring at room temperature for 4 hours. The reaction solution was purified by silica gel column chromatography to obtain PNT-69 NHS product (PNT-70) in which the carboxyl group at the end of the PEG chain (PEG12) was activated (NHS esterification).

[0268] [Synthesis Example 2] Synthesis of Polymer C

[0269]

[0270] First, 2-aminoethyl methacrylate hydrochloride, (4-vinylphenyl)methaneamine, and methacryloylcholine chloride were prepared. Then, 0.97 mmol of 2-aminoethyl methacrylate hydrochloride, 0.97 mmol of (4-vinylphenyl)methaneamine, 11.97 mmol of methacryloylcholine chloride, 0.08 mmol of V-50, and 10.49 g of ethanol were added to a 4-necked flask. The same treatment as that of polymer A was then performed to obtain polymer C. The molar ratio of polymer C was calculated based on the results of 1H-NMR, and the result was a polymer corresponding to n:m:l=21.2:8.1:70.7. In addition, the number average molecular weight Mn of the polymer was 37774, and the weight average molecular weight Mw was 214367 as measured by gel permeation chromatography (GPC).

[0271] [Synthesis Example 3] Synthesis of polymer-bonded PNT1

[0272] PNT-69NHS (PNT-70) was dissolved in MilliQ water to 21.05 mg / mL (liquid (1)). Polymer C, a high molecular weight polymer, was dissolved in MilliQ water to 15 mg / mL (liquid (2)). Then, WSC (DOJINDOW001) was dissolved in MilliQ water to 20 mg / mL (liquid (3)). 40 μL of liquid (1), 140.3 μL of liquid (2), 383.4 μL of liquid (3), and 96 μL of a separately prepared 250 mM 2-morpholinoethanesulfonic acid (MES) buffer (pH 6.0) were mixed and adjusted to a total volume of 1200 μL with MilliQ water. Thereafter, the mixture was reacted at room temperature with stirring for about 20 hours. Thereafter, ultrafiltration was performed several times using a centrifugal ultrafiltration filter (Amicon Ultra-4 50k; MERCK MILLIPORE), and the liquid from which low molecular weight molecules were removed was recovered.

[0273] [Synthesis Example 4] Synthesis of polymer-bonded PNT2

[0274] PNT-69NHS (PNT-70) was dissolved in MilliQ water to 15 mg / mL (liquid (1)). Poly(L-lysine) hydrochloride (ALAMANDA POLYMERS PLKC800), a high molecular weight polymer, was dissolved in MilliQ water to 10 mg / mL (liquid (2)). Then, WSC (DOJINDO W001) was dissolved in MilliQ water to 20 mg / mL (liquid (3)). 43.7 μL of liquid (1), 51.3 μL of liquid (2), 479.3 μL of liquid (3), and 96 μL of a separately prepared 250 mM 2-morpholinoethanesulfonic acid (MES) buffer (pH 6.0) were mixed and adjusted to a total volume of 1200 μL with MilliQ water. Thereafter, the mixture was reacted at room temperature with stirring for about 20 hours. Thereafter, ultrafiltration was performed several times using a centrifugal ultrafiltration filter (Amicon Ultra-4 50k; MERCKMILLIPORE), and a liquid from which low molecular weight molecules had been removed was recovered.

[0275] (d) Oxidoreductase

[0276] (d-1) FAD-dependent glucose dehydrogenase…GDH GLD1: manufactured by BBI International

[0277] (e) Cross-linking agent

[0278] (e-1) Glutaraldehyde…Glutaraldehyde 25% solution (Fujifilm Wako Pure Chemical Industries, Ltd.)

[0279] (f) Buffer

[0280] (f-1) Bis-Tris: (Bis(2-hydroxyethyl)iminotris(hydroxymethyl)methane)…Made by Dojin Chemical Co., Ltd.

[0281] (f-2A) Tris-HCl pH7.5…Invitrogen UltraPure 1M Tris-HCl pH7.5, ThermoFisher SCIENTIFIC Company

[0282] (f-2B) Tris-HCl pH8.0…Invitrogen UltraPure 1M Tris-HCl pH8.0, ThermoFisher SCIENTIFIC Company

[0283] (f-2C) Tris-HCl pH 8.5…1M Tris-HCl (pH 8.5), Fujifilm Wako Pure Chemical Industries, Ltd. (Manufacturer: NIPPON GENE Co., Ltd.)

[0284] (g) Metal salts

[0285] Sodium chloride (NaCl)…Fujifilm Wako Pure Chemical Industries, Ltd. (Product No.: 191-01665)

[0286] Potassium chloride (KCl)…Nacalai Tesque Co., Ltd. (Product No.: 28514-75)

[0287] Sodium bromide (NaBr)…Fujifilm Wako Pure Chemical Industries, Ltd. (Product No.: 192-09412)

[0288] Potassium bromide (KBr)…Fujifilm Wako Pure Chemical Industries, Ltd. (Product No.: 164-03472)

[0289] Magnesium bromide (MgBr2) hexahydrate…Fujifilm Wako Pure Chemical Industries, Ltd. (Product No.: 138-09192, purity 99.9%)

[0290] Potassium sulfate (K2SO4)…Fujifilm Wako Pure Chemical Industries, Ltd. (Product No.: 169-13552, purity 99.9%)

[0291] [Test Example 1] Dispersibility Test

[0292] <Preparation of reagent solution samples>

[0293] According to the formulation shown in Table 2, carbon black (a-1) was added to an aqueous solution of various anionic dispersants (b) at a concentration of 1 mg / mL or 2 mg / mL to make the carbon concentration 20 mg / mL, and then treated with an ultrasonic homogenizer for more than 3 minutes to prepare a reagent solution sample.

[0294]

[0295] <Filter treatment of reagent solution>

[0296] The reagent solution sample obtained as described above was treated in an ultrasonic bath for about 10 minutes before use. The obtained redispersion solution sample was filtered through a 0.8 μm filter (ADVANTEC, DISMIC 25CS080AN), and the recovered filtrate was diluted 10 times with Milli-Q water to prepare a recovered solution sample.

[0297] The captured image of the recovered liquid sample is displayed on Figure 8The lighter the color of the recovery liquid sample, the less carbon black (a-1) passes through the filter, and the more carbon black (a-1) is agglomerated and captured by the filter, that is, the smaller the dispersibility. However, regardless of which anionic dispersant (b) is used in the reagent solution (recovery liquid) samples 1-1 to 1-11, although there are differences in degree, they all show the effect of dispersing the conductive carbon filler (a) in the aqueous solvent. In addition, based on the results of the reagent solution (recovery liquid) samples 1-1 to 1-3 using poly(acrylic acid) with different average molecular weights as the anionic dispersant (b) at the same concentration (1 mg / mL), the following suggestion is given, that is, when an anionic polymer such as poly(acrylic acid) is used as the anionic dispersant (b), if its average molecular weight becomes larger, the dispersing effect of the conductive carbon filler (a) becomes smaller.

[0298] [Test Example 2] pH and metal ion concentration dependence test 1

[0299] According to the formulation shown in Table 3, reagent solution samples containing various components at given concentrations were prepared. The buffer solution used was prepared so that the pH of the reagent solution would be a given value when used in a given amount. It should be noted that Test Example 2 is a test example in which the dispersibility of reagent solution samples containing metal ions (metal salts) at the same concentration was compared after the pH was adjusted using a buffer solution containing no metal ions (metal salts).

[0300] Regarding the concentration of polymer-bonded PNT, first dilute the stock solution of each polymer-bonded PNT 25 times and then add 100μL to the microplate. Use a microplate reader to measure the absorption spectrum to confirm the concentration of the stock solution, and adjust the concentration in each reagent sample based on this value. A value such as "equivalent to absorbance 3" means that the absorbance at 608nm is about 0.12 when diluted 25 times. Here, the microplate used is the UV-Star (registered trademark) 96Well F-Boden manufactured by Greiner Bio-One. In addition, the microplate reader used is the infinite (registered trademark) M200 Pro manufactured by TECAN.

[0301]

[0302] The preparation of the reagent solution sample was performed as follows. First, the conductive carbon filler (a) was added to the aqueous solution of the anionic dispersant (b), and then treated with an ultrasonic homogenizer for more than 3 minutes, and a buffer solution (f) and a metal salt (g) were added thereto. Then, the cationic mediator (c) was added to the treated solution, and then treated with an ultrasonic homogenizer for about 30 seconds. The presence or absence of aggregation of the obtained reagent solution sample was confirmed by visual inspection. The results are shown in Table 3.

[0303] [Test Example 3] pH and metal ion concentration dependence test 2

[0304] Reagent solution samples containing various components at given concentrations were prepared according to the formulation shown in Table 4. It should be noted that Test Example 3 is a test example for comparing the dispersibility of reagent solution samples containing metal ions (metal salts) at different concentrations after adjusting the pH using a buffer solution that does not contain metal ions (metal salts).

[0305]

[0306] The preparation of the reagent solution sample was performed as follows. First, the conductive carbon filler (a) was added to the aqueous solution of the anionic dispersant (b), and then the solution was treated with an ultrasonic homogenizer for more than 3 minutes, and a buffer solution (f) and a metal salt (g) were added thereto. Then, the cationic mediator (c) was added to the treated solution, and then the solution was treated with an ultrasonic homogenizer for about 30 seconds. The presence or absence of aggregation of the obtained reagent solution sample was visually confirmed. The results are shown in Table 4.

[0307] [Test Example 4] pH and metal ion concentration dependence test 3

[0308] Reagent solution samples containing various components at given concentrations were prepared according to the formulation shown in Table 5. It should be noted that Test Example 4 is a test example for comparing the dispersibility of reagent solution samples containing metal salts (metal ions) of different types and concentrations after pH adjustment using a buffer solution containing no metal ions (metal salts).

[0309]

[0310] The sample of the reagent solution is prepared as follows. First, the conductive carbon filler (a) is added to the aqueous solution of the anionic dispersant (b), and then treated with an ultrasonic homogenizer for more than 3 minutes, and then a buffer solution (f) and a metal salt (g) are added thereto. Then, a cationic mediator (c) is added to the treated solution, and then treated with an ultrasonic homogenizer for about 30 seconds.

[0311] The presence or absence of aggregation of the obtained reagent solution sample was confirmed by visual inspection. The results are shown in Table 5. Regarding the results of Test Examples 2 to 4, first, it can be seen from the results of Test Example 2 that although aggregation also occurs when the pH of the reagent solution is high (not due to the influence of the concentration of the metal salt in the buffer solution used for pH adjustment, but due to the influence of the pH itself), within the appropriate pH range corresponding to the composition of the reagent solution, the dispersibility of the conductive carbon filler can be improved and aggregation can be suppressed. In addition, it can be seen from the results of Test Examples 3 and 4 that although the occurrence of coagulation varies depending on the type of metal ions contained in the reagent solution, in general, there is a tendency for coagulation to occur when the concentration of metal ions is high. For example, if the concentration of metal ions is less than 100 mM, coagulation can be suppressed for most metal ions. On the other hand, there are also cases where coagulation can be suppressed even if the concentration is higher than 50 mM (for example, about 200 mM), such as magnesium ions. Therefore, within the appropriate concentration range corresponding to the type of metal ions, the dispersibility of the conductive carbon filler can be improved and coagulation can be suppressed.

[0312] [Test Example 5] Test of anionic dispersant (b)

[0313] According to the formulation shown in Table 6, reagent solution samples containing various components at given concentrations were prepared.

[0314]

[0315] The test liquid sample was prepared as follows. First, the conductive carbon filler (a) was added to the aqueous solution of the anionic dispersant (b), and then treated with an ultrasonic homogenizer for more than 3 minutes, and a buffer solution (f) was added thereto. Then, the cationic mediator (c) was added to the treated solution, and then treated with an ultrasonic homogenizer for about 30 seconds. Finally, the oxidoreductase (d) and the crosslinking agent (e) were added to the treated solution.

[0316] The presence or absence of aggregation of the obtained test solution sample was confirmed by visual inspection. The results are shown in Table 6. When the polymer-bonded PNT1 synthesized using a given copolymer as the cationic polymer (c) and the polymer-bonded PNT2 synthesized using PLL as the cationic polymer (c) were used, differences were observed in the effect of improving the dispersibility of the conductive carbon filler (a) depending on the concentration in the reagent solution and the pH of the reagent solution. However, no matter which cationic polymer (c) was used, there were conditions under which the effect of improving the dispersibility of the conductive carbon filler (a) could be observed.

[0317] [Test Example 6] Responsiveness evaluation test

[0318] <Preparation of reagent solution>

[0319] According to the formulation shown in Table 7, reagent solution samples containing various components at given concentrations were prepared.

[0320]

[0321] The test liquid sample is prepared as follows. First, a conductive carbon filler (a) is added to an aqueous solution of an anionic dispersant (b) or a control thereof, and then the solution is treated with an ultrasonic homogenizer for more than 3 minutes, and a buffer solution (f) is added thereto. Then, a cationic mediator (c) is added to the treated solution, and the solution is treated with an ultrasonic homogenizer for about 30 seconds. Finally, an oxidoreductase (d) and a crosslinking agent (e) are added to the treated solution.

[0322] <Fabrication of Sensor Electrodes>

[0323] A carbon electrode was prepared on an insulating substrate by screen printing, and 0.6 μL of each reagent solution sample prepared as described above was applied to the obtained carbon electrode and dried overnight to obtain a sensor electrode.

[0324] <Preparation of RPMI medium>

[0325] 2-Morpholinoethanesulfonic acid (MES, manufactured by Dojindo Chemical Co., Ltd.) and 3-Morpholinopropanesulfonic acid (MOPS, manufactured by Dojindo Chemical Co., Ltd.) were added as buffer components to a solution prepared using RPMI-1640 Medium (R1383 manufactured by Sigma Aldrich Co., Ltd.) so that the final concentrations of each were 25 mM, and the pH was adjusted to 7.4. The medium thus obtained was used as the "RPMI medium" in the following examples.

[0326] <Evaluation of sensor responsiveness>

[0327] For a three-electrode measurement system using the sensor electrode prepared as described above as a working electrode and a platinum electrode as a counter electrode and an Ag / AgCl electrode (saturated KCl) (manufactured by BAS) as a reference electrode, a potentiostat (manufactured by BAS) was used to measure the time change (current response value) of the current in the RPMI culture medium at about 37°C by amperometry. Specifically, glucose was added every 100 seconds after 100 seconds from the start of the measurement so that the theoretical value was 3mM, 15mM or 30mM, and the current response value was measured. The current response value was set to: the average value calculated from the measured values ​​of 5 points before the next addition of glucose, 5 seconds before, 10 seconds before, 15 seconds before, 20 seconds before, and 25 seconds before the addition of glucose to be the object of measurement. In addition, the current value of the final concentration was set to: the average value calculated from the measured values ​​of 5 points after 80 seconds, 85 seconds after, 90 seconds after, 95 seconds after, and 100 seconds after the addition of glucose solution to make the glucose concentration 30mM. It should be noted that the current value at each glucose concentration is a current value obtained by subtracting the current value at a glucose concentration of 0 mM from the background correction process.

[0328] In addition, cyclic voltammetry was performed in RPMI medium using the same three-electrode measurement system at a scan rate of 10 mV / s. It should be noted that both the current response value and the cyclic voltammetry result are the average of the measurement values ​​of the two sensors.

[0329] The result of the current response value is expressed as Fig. 9 In [A], the results of cyclic voltammetry are shown in Fig. 9 [B] In the middle. Regarding the current responsiveness, the sensors using each anionic dispersant (anionic polymer) (reagent solution samples 6-1 to 6-5) showed higher responsiveness than the sensor using hydroxypropyl cellulose (reagent solution sample 6-6). Similarly, regarding the results of cyclic voltammetry, the sensors using each anionic dispersant (anionic polymer) obtained higher redox peaks than the sensor using hydroxypropyl cellulose. This can be inferred to be because the use of anionic dispersants (anionic polymers) allows the mediator to be closely adsorbed on the electrode.

[0330] [Test Example 7] Durability (Response Retention Rate) Evaluation Test

[0331] <Preparation of reagent solution>

[0332] In Test Example 7, the reagent solution samples 6-1 and 6-6 in Test Example 6 were prepared again and used.

[0333] <Preparation of polymer solution for protective film>

[0334] Each reagent shown below was mixed to give the following final concentrations to prepare a protective film polymer solution.

[0335] Poly(tert-butyl methacrylate-b-4-vinylpyridine) (manufactured by Polymer Source, hereinafter referred to as "tBuMA4VP") Final concentration: 7.11% (wt / v)

[0336] · Random copolymer of tripropylene glycol methyl ether methacrylate and styrene-4-vinylpyridine (manufactured by NARD, hereinafter referred to as "TGMAS4VP") Final concentration: 0.89% (wt / v)

[0337] · Poly(ethylene glycol) diglycidyl ether (manufactured by Sigma Aldrich, hereinafter referred to as "PEGDGE") Final concentration: 0.98% (wt / v)

[0338] HEPES buffer (pH 8.0) Final concentration: 5 mM

[0339] It should be noted that tBuMA4VP, TGMAS4VP and PEGDGE were dissolved in ethanol and used. The number average molecular weight Mn of tBuMA4VP was 87,000 for poly(tert-butyl methacrylate) and 74,000 for poly(4-vinylpyridine). The Mw / Mn of tBuMA4VP was 1.16. For TGMAS4VP, tripropylene glycol methyl ether methacrylate: styrene: 4-vinylpyridine = 6.6: 20.3: 73.0, the number average molecular weight Mn was 60,704, the weight average molecular weight Mw was 120,095, and the Mw / Mn was 1.98. The number average molecular weight Mn of PEGDGE was ∼1,000. The HEPES buffer was prepared using 2-[4-(2-hydroxyethyl)-1-piperazinyl]ethanesulfonic acid (manufactured by Dojin Chemical Co., Ltd.).

[0340] <Fabrication of Sensor Electrodes>

[0341] Gold electrodes are made by sputtering on an insulating substrate. On the obtained gold electrodes, 0.5 μL of the reagent solution sample prepared as described above is applied and dried for 15 minutes. This operation is repeated twice for a total of 3 applications. Thereafter, it is dried overnight. Thus, a reagent layer corresponding to each reagent solution sample is formed on each gold electrode. Each gold electrode formed with a reagent layer is immersed in a protective film polymer solution prepared as described above, and the operation of pulling and drying is repeated several times to form a protective film on each gold electrode. Using the above process, a sensor electrode is obtained.

[0342] <Sensor evaluation regarding durability (response retention rate)>

[0343] For a three-electrode measurement system in which the sensor electrode prepared as described above is used as the working electrode and a platinum electrode as the counter electrode and an Ag / AgCl electrode (saturated KCl) (manufactured by BAS) as the reference electrode are combined, a potentiostat (manufactured by BAS) is used to measure the time change of the current in the RPMI medium at about 37°C by amperometry. Specifically, glucose is added every 1000 seconds after 1500 seconds from the start of the measurement, so that the theoretical value is 5mM, 15mM or 30mM, and the current response value is continuously measured. After the measurement, the electrode is stored in the RPMI medium at 37°C. In addition, the same measurement is performed on the first, second and third days after storage. It should be noted that the current value at the glucose concentration of 5mM and 15mM is: after the addition of the glucose to be measured, the average value is calculated based on the measured values ​​of 5 points before the next addition of glucose, 5 seconds before, 10 seconds before, 15 seconds before, 20 seconds before and 25 seconds before. The current value at the final concentration is the average value calculated from the measured values ​​at 980 seconds, 985 seconds, 990 seconds, 995 seconds, and 1000 seconds after adding the glucose solution to make the glucose concentration 30 mM. The current value at each glucose concentration is the current value after background correction processing is performed by subtracting the current value at the glucose concentration of 0 mM.

[0344] The results are expressed in Fig.10 After the protective film was applied, the sensor using poly(acrylic acid) (reagent solution sample 6-1) showed higher values ​​for current responsiveness than the sensor using hydroxypropyl cellulose (reagent solution sample 6-6). In addition, regarding sensor durability after 3 days (current retention rate relative to the first day), the sensor using poly(acrylic acid) (reagent solution sample 6-1) also showed higher values. This is presumably because the mediator is more firmly adsorbed on the electrode.

Claims

1. A reagent layer comprising a conductive carbon filler (a), an anionic dispersant (b) and a cationic mediator (c).

2. The reagent layer according to claim 1, wherein The anionic dispersant (b) is a polymer having a weight average molecular weight of 70,000 or less.

3. The reagent layer according to claim 1, wherein The anionic dispersant (b) is a polymer having a carboxyl group and / or a sulfonic group in a side chain.

4. The reagent layer according to claim 3, wherein The anionic dispersant (b) is a polymer including at least one selected from the group consisting of a unit derived from acrylic acid, a unit derived from maleic acid, and a unit derived from styrenesulfonic acid.

5. The reagent layer according to claim 1, wherein The cationic mediator (c) is a compound in which a redox mediator compound (c1) and a cationic polymer (c2) are bonded via a linker (c3) as necessary.

6. The reagent layer according to claim 5, wherein The cationic polymer (c2) has a quaternary ammonium cationic group.

7. The reagent layer according to claim 1, wherein The conductive carbon filler (a) is carbon black. 8 . The reagent layer according to claim 1 , further comprising an oxidoreductase (e) that oxidizes or reduces the analyte.

9. The reagent layer according to claim 8, wherein The oxidoreductase (e) is a coenzyme-binding oxidoreductase.

10. The reagent layer according to claim 8, wherein The oxidoreductase (e) is cross-linked with the cationic polymer (c2). 11 . An electrochemical sensor for detecting or quantifying an analyte, comprising a working electrode, a counter electrode, and a reagent layer according to claim 1 . The electrochemical sensor according to claim 11 , further comprising a reference electrode. 13 . The electrochemical sensor according to claim 11 , further comprising a protective film covering at least the reagent layer.

14. A method for forming a reagent layer, the method comprising: (1) a step of preparing a reagent solution containing a conductive carbon filler (a), an anionic dispersant (b), and a cationic mediator (c); (2) applying the reagent solution to the reagent layer formation site; and (3) A step of drying the applied reagent solution to form a reagent layer.

15. The method for forming a reagent layer according to claim 14, wherein: The pH of the reagent solution is 8.0 or less.

16. The method for forming a reagent layer according to claim 15, wherein: The concentration of the metal ions in the reagent solution is 200 mM or less.

17. The method for forming a reagent layer according to claim 16, wherein: The metal ions in the reagent solution are alkali metal ions, and the concentration of the metal ions is less than 100 mM.

18. The method for forming a reagent layer according to claim 14, wherein: The anionic dispersant (b) is a polymer having a weight average molecular weight of 70,000 or less and including at least one selected from the group consisting of a unit derived from acrylic acid, a unit derived from maleic acid, and a unit derived from styrene sulfonic acid.

19. The method for forming a reagent layer according to claim 14, wherein: The cationic mediator (c) is a compound in which a redox mediator compound (c1) and a cationic polymer (c2) having a quaternary ammonium cationic group are bonded via a linker (c3) as necessary.

Citation Information

Patent Citations

  • Enzyme electrode and biosensor, and biofuel cell

    JP2021082394A

  • Biofuel cell, method for manufacturing biofuel cell, electronic device, enzyme-immobilized electrode, method for producing enzyme-immobilized electrode, electrode for production of enzyme-immobilized electrode, method for producing electrode for production of enzyme-immobilized electrode, and enzyme reaction-utilizing apparatus

    WO2013065581A1